Transparent, fracture-resistant polymerization resins for production of dental moldings

JP2022173073A5Active Publication Date: 2025-04-04IVOCLAR VIVADENT AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022059245
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-07
Filing Date
2022-03-31
Publication Date
2025-04-04
Estimated Expiration
2042-03-31

AI Technical Summary

Technical Problem

Existing dental polymer materials have volume shrinkage problems during polymerization, resulting in marginal gap and dimensional instability, while it is difficult to take into account high transparency, good fracture toughness and mechanical properties.

Method used

The radiation polymerizable composition containing ABA or AB type block copolymers is used to combine monofunctional polymerizable monomers and polyurethane di(meth)acrylate long chains to optimize the transparency, fracture toughness and mechanical properties of the material.

Benefits of technology

It achieves high transparency, good fracture toughness and mechanical properties, while reducing polymer volume shrinkage, and is suitable for the production of dental restoration materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2022173073000001
    Figure 2022173073000001
  • Figure 2022173073000002
    Figure 2022173073000002
  • Figure 2022173073000003
    Figure 2022173073000003
Patent Text Reader

Abstract

To provide transparent, fracture-resistant polymerization resins for the production of dental moldings.SOLUTION: A radically polymerizable dental material contains at least one ABA or AB block copolymer, preferably at least one monofunctional, radically polymerizable monomer (a), and preferably at least one radically polymerizable urethane di(meth)acrylate telechel (b). The object of the invention is to provide materials for the production of dental moldings which have a property profile optimized for additive processes. In particular, the materials should have high transparency in combination with good fracture toughness and high work of fracture. In addition, they should exhibit a low viscosity and good mechanical properties after storage in water, as well as good biocompatibility.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] field The present invention relates to a radical polymerizable composition particularly suitable as a dental material for producing dental molded articles such as artificial teeth, dental prostheses, inlays, onlays, splints (bite splints), crowns, bridges, veneer materials, and dental orthodontic appliances by additive processes. [Background technology]

[0002] Background information Most conventional dental polymerization systems consist of a mixture of transparent liquid monomers, initiator components, stabilizers, and pigments (J. Viohl, K. Dermann, D. Quast, S. Venz, Die Chemie zahnarztlicher Fullungskunststoffe, Carl Hanser Verlag, Munich-Vienna 1986, 21-27). Dimethacrylate mixtures are mostly used as monomers to construct polymer networks in filling materials, for example (see A. Peutzfeldt, Resin composites in dentistry: The monomer systems, Eur. J. Oral. Sci. 105 (1997) 97-116; N. Moszner, T. Hirt, New Polymer-Chemical Developments in Clinical Dental Polymer Materials: Enamel-Dentin Adhesives and Restorative Composites, J. Polym. Sci. Part A: Polym. Chem. 50 (2012) 4369-4402). Examples of these include the high-viscosity dimethacrylates 2,2-bis[4-(2-hydroxy-3-methacryloyloxypropyl)phenyl]propane (bis-GMA) and 1,6-bis-[2-methacryloyloxyethoxycarbonylamino]-2,4,4-trimethylhexane (UDMA), which are used as diluent monomers, as well as the low-viscosity dimethacrylates bismethacryloyloxymethyltricyclo[5.2.1.]decane (TCDMA), decanediol-1,10-dimethacrylate (D3MA), and triethylene glycol dimethacrylate (TEGDMA). In contrast, the monofunctional monomer methyl methacrylate (MMA) has low viscosity but is highly volatile and is mainly used in dental prosthetics.

[0003] Depending on the application, other additives and initiators suitable for initiating radical polymerization are added. Visible light initiators, which form radicals with blue light and are characterized by good curing depth and very good whitening properties, are used to initiate polymerization using light. Prosthetic materials contain powdered polymethyl methacrylate (PMMA) as an essential component, which forms a paste with MMA. Curing is carried out using heat or redox initiators. In the case of filling composites and routing cements, a high proportion of inorganic filler results in high flexural strength and surface hardness, however, the filler may have an unfavorable effect on transparency.

[0004] A major problem with radical methacrylate polymers is the polymerization shrinkage (ΔV) that occurs during the polymerization of the methacrylate monomer used. P ), that is, volume shrinkage, which in the case of filling composites may lead to the formation of very unfavorable marginal gaps, for example, and in the case of prosthetic materials, it adversely affects dimensional stability (ΔV P (For example, in the case of pure MMA, this is 21.0% by volume).

[0005] Another disadvantage of PMMA or dimethacrylate polymers is their high level of brittleness. Low fracture toughness is an inherent property of amorphous PMMA glass, and is caused, in particular, by their highly irregular network structure in polymer networks formed by dimethacrylate mixtures.

[0006] In recent years, additive manufacturing processes have attracted increasing attention and have been widely used for the production of dental molded bodies. In additive manufacturing processes, sometimes called production-capable manufacturing processes, 3D molded bodies are created in layers from polymerizable materials, starting from a CAD data set, and the layers are cured by exposure control. In stereolithography (SL), a UV laser is used as the light source. In DLP processes (digital light processing), a projectable image is used to cure the layered photopolymerized resin.

[0007] Building materials for additive production of dental molded bodies must meet a variety of requirements, given the unique characteristics of this process. They should have low viscosity, as well as high transparency and good mechanical properties after curing. Materials disclosed in the current art are often optimized for specific properties, at the expense of others.

[0008] The use of monofunctional and polyfunctional methacrylates as resins in additive processes is the subject of numerous patents and patent applications.

[0009] US 10,562,995 B2 discloses a polymerization resin for the production of stereolithographic dental prostheses, based on a mixture of an aromatic di(meth)acrylate without OH or COOH groups and a (meth)acrylic monomer containing at least one OH or COOH group.

[0010] US 10,568,814 B2 discloses photopolymerizable compositions for the production of artificial teeth and denture bases by 3D printing, which are said to have high flexural strength and high modulus of elasticity after curing. The material is based on a mixture of ethoxylated bisphenol A dimethacrylate, monofunctional methacrylate, and urethane dimethacrylate.

[0011] EP 3 020 361 A1 relates to a curable composition for additive manufacturing processes containing radically polymerizable polysiloxanes and disiloxanes. The material is said to be characterized by high dimensional stability and improved biocompatibility.

[0012] EP 3 494 954 A1 discloses a photopolymerizable composition for the production of dental prostheses, comprising a mixture of an aromatic acrylate having a molar mass of 200-800 g / mol and at least one other (meth)acrylate that may contain aromatic and non-aromatic rings. The material is said to be characterized by good Charpy fracture toughness.

[0013] EP 3 564 206 A1 discloses (meth)acrylooxy-substituted benzoic acid esters that are said to be suitable as reactive diluents for additive manufacturing processes.

[0014] Dental molded articles must possess good fracture toughness, along with good flexural strength and a high modulus of elasticity. Improvement of fracture toughness can be achieved, for example, through internal plasticization by adding flexible monomers. However, this has the disadvantage of significantly reducing the flexural strength and modulus of elasticity of the polymer. Therefore, according to the prior art, polymer particles having a core-shell structure that yields relatively good flexural strength and a relatively high modulus of elasticity are usually added to the polymerized resin as a so-called impact resistance modifier to improve fracture toughness.

[0015] WO 2014 / 078537 A1 discloses resin mixtures based on monofunctional and polyfunctional methacrylates for the production of dental molded bodies by a 3D printing process, which contain a silicone acrylate-based impact modifier having a core-shell structure for improving impact resistance and fracture toughness.

[0016] US 2018 / 0000570 A1 relates to monofunctional and polyfunctional (meth)acrylate-based building materials for additive production of dental components. The building materials contain silicone acrylic-based rubber particles (product S2006 from Mitsubishi Rayon Co., Ltd.) having a core-shell structure as an impact modifier, as well as oligomers prepared by reacting trimethyl 1,6-diisocyanate, bisphenol A propoxylate, and 2-hydroxyethyl methacrylate (HEMA). The cured components are said to have good mechanical and physical properties as well as good biocompatibility.

[0017] US 10,299,896 B2 and US 2019 / 0053883 A1 disclose dental components produced by an additive process, having at least two layers of building materials having different compositions. One layer is formed of a material containing an oligomer obtained by reacting an intermediate product having terminal isocyanate groups with a hydroxyl-based methacrylate, a polymerizable acrylic compound, and an impact modifier. Another at least one layer is formed of a material containing a urethane monomer, a glycol dimethacrylate, and a filler. Combinations of materials having different mechanical and physical properties are said to be advantageous for adapting components to different requirements. For example, commercially available polymers with a core-shell structure, such as product M570 from Kaneka, are used as impact modifiers.

[0018] EP 3 564 282 A1 discloses curable compositions for high-temperature photopolymerization processes, containing an oligomeric urethane dimethacrylate as a glass transition temperature modifier, a (poly)carbonate-(poly)urethane dimethacrylate as a toughness modifier, and optionally containing core-shell particles. These compositions are said to have good thermomechanical properties and good biocompatibility, making them suitable for the production of dental orthodontic appliances.

[0019] The mechanism of action of impact modifiers with a core-shell structure is based on the interaction between the crack tip during formation and core-shell polymer particles. These particles have a relatively soft polymer core and a hard polymer shell. When a crack tip encounters such particles, a cavity is formed in the core, the polymer shell separates from the polymer matrix, and further the core separates from the shell, thus creating a gap for the plastically deformed surface (cavitation). A significant disadvantage for dental applications is that core-shell polymers (CSPs) significantly reduce the transparency of the material, adversely affecting the stereolithographic construction process. [Prior art documents] [Patent Documents]

[0020] [Patent Document 1] U.S. Patent No. 10,562,995 [Patent Document 2] U.S. Patent No. 10,568,814 [Patent Document 3] European Patent Application Publication No. 3020361 [Patent Document 4] European Patent Application Publication No. 3,494,954 [Patent Document 5] European Patent Application Publication No. 3 564 206 [Patent Document 6] International Publication No. 2014 / 078537 [Patent Document 7] U.S. Patent Application Publication No. 2018 / 0000570 [Patent Document 8] U.S. Patent No. 10,299,896 [Patent Document 9] U.S. Patent Application Publication No. 2019 / 0053883 [Patent Document 10] European Patent Application Publication No. 3 564 282 [Non-patent literature]

[0021] [Non-Patent Document 1] J. Viohl, K. Dermann, D. Quast, S. Venz, Die Chemie zahnarztlicher Fullungskunststoffe, Carl Hanser Verlag, Munich-Vienna1986, 21-27 [Non-Patent Document 2] A. Peutzfeldt, Resin composites in dentistry: The monomer systems, Eur. J. Oral. Sci. 105 (1997) 97-116 [Non-Patent Document 3] N. Moszner, T. Hirt, New Polymer-Chemical Developments in Clinical Dental Polymer Materials: Enamel-Dentin Adhesives and Restorative Composites, J. Polym. Sci. Part A: Polym. Chem. 50 (2012) 4369-4402 [Overview of the project] [Means for solving the problem]

[0022] The object of the present invention is to provide a material for producing dental molded articles having a property profile optimized for additive processes. In particular, the material should have high transparency, along with good fracture toughness and high fracture work. Furthermore, they should exhibit low viscosity and good mechanical properties, as well as good biocompatibility, after storage in water.

[0023] According to the present invention, this objective is achieved by a radically polymerizable dental material containing at least one ABA or AB block copolymer. Furthermore, the dental material preferably contains at least one monofunctional radically polymerizable monomer (a) and preferably also contains at least one radically polymerizable urethane di(meth)acrylate telekel (b). This application provides, for example, the following items: (Reclaim) (Item 1) A radically polymerizable dental material comprising at least one ABA or AB block copolymer, preferably at least one monofunctional radical polymerizable monomer (a), and preferably at least one radical polymerizable urethane di(meth)acrylate telekel (b). (Item 2) In all cases, relative to the total mass of the aforementioned material, (a) 30-70% by weight, preferably 30-61% by weight, particularly preferably 40-60% by weight, at least one aromatic bicyclic or tricyclic mono(meth)acrylate, (b) 20-60% by weight, preferably 30-55% by weight, particularly preferably 33-55% by weight, of at least one urethane di(meth)acrylate telekel having a number average molar mass of 750-2000 g / mol, (c) 0 to 30% by weight, preferably 0 to 20% by weight, particularly preferably 0% by weight, di(meth)acrylate monomer(s) (d) At least one ABA and / or AB block copolymer in an amount of 1 to 12% by weight, preferably 2 to 12% by weight, and particularly preferably 2 to 10% by weight, wherein the A block (or more) is homogeneous miscible with the mixture of components (a) to (c), and the B block is not homogeneous miscible with the mixture of components (a) to (c), and (e) 0.1 to 5.0% by weight, preferably 0.2 to 4.0% by weight, and particularly preferably 0.3 to 3.0% by weight, at least one initiator for radical polymerization. Radical polymerizable dental materials as described in item 1, including those listed in item 1. (Item 3) Component (a) is at least one aromatic bicyclic or tricyclic monomethacrylate of formula (I). [ka] [In the formula, the variable elements have the following meanings: A is an aromatic group having 6 to 15 carbon atoms or a bicyclic or tricyclic aliphatic group having 7 to 10 carbon atoms, and A may be unsubstituted or substituted with one or more C1-C5 alkyl groups, C1-C5 alkoxy groups and / or chlorine atoms; R is either hydrogen or methyl; X 1 , X 2 These are mutually independent, neither present in any case, or are ether, ester, or urethane groups, and Y1 When X does not exist 1 does not exist, and Y 2 When X does not exist 2 does not exist; Y 1 and Y 2 are each independently a branched or preferably linear aliphatic hydrocarbon radical having 1 to 10 carbon atoms which may be interrupted by 1 to 3 oxygen atoms and which in any case do not exist] A dental material according to any one of the preceding items, comprising (Item 4) As component (a), 2 - phenoxyethyl (meth)acrylate, 2-(o - biphenyloxy)ethyl (meth)acrylate, 2 - hydroxy - 3 - phenoxypropyl (meth)acrylate, phenethyl (meth)acrylate, 2 - [(benzyloxycarbonyl)-amino]-ethyl (meth)acrylate, 2 - [(benzylcarbamoyl)-oxy]-ethyl (meth)acrylate, 1 - phenoxypropan - 2 - yl (meth)acrylate and 2-(p - cumylphenoxy)-ethyl (meth)acrylate, 2-(benzyloxy)ethyl (meth)acrylate, 3 - phenoxybenzyl (meth)acrylate, phenoxypropyl (meth)acrylate, 2 - benzyloxyethyl (meth)acrylate, 2 - benzoyloxyethyl (meth)acrylate, 2 - (meth)acryloyloxybenzoic acid methyl ester, tricyclodecane (meth)acrylate, tricyclodecane methyl (meth)acrylate, 2-(p - cumylphenoxy)ethyl (meth)acrylate, 4,7,7 - trimethylbicyclo[2.2.1]heptanyl (meth)acrylate, octahydro - 1H - 4,7 - methanoinden - 5 - yl (meth)acrylate or a mixture thereof. A dental material according to any one of the preceding items. (Item 5) The dental material according to any one of the preceding items, comprising as component (b) at least one urethane dimethacrylate telekel obtainable by reacting a diisocyanate with a diol, and then reacting an α,ω-isocyanate-functionalized urethane telekel with HEMA or HPMA. (Item 6) Component (b) is Telekel by general formula (II). [ka] [In the formula, the variable elements have the following meanings: R 1 , R 2 These are independent of each other and in each case are H or methyl, preferably methyl. R 3 , R 4 These are independent of each other and in each case are H or methyl, preferably methyl. x and y are independent of each other and are integers from 1 to 11, preferably from 1 to 5, in both cases. n is 1, 2, or 3, preferably 1. Z is [ka] Preferably [ka] And, DA is a structural element derived from the diol HO-DA-OH, obtained by cleaving the hydrogen atom from the hydroxyl group, and the diol HO-DA-OH is one of the following compounds: ethoxylated or propoxylated bisphenol A having 2 to 6 ethoxy or propoxy groups, o-diphenyl or p-diphenyl, and C2-C2 compounds that can contain 1 to 4 O or S atoms in their carbon chain. 18Alkanediols, preferably selected from ethoxylated or propoxylated bisphenol A having 2, 3 or 4 ethoxy or propoxy groups, hexane-1,6-diol, octane-1,8-diol, nonane-1,9-diol, decane-1,10-diol, undecanediol or dodecane-1,12-diol, tetra or pentaethylene glycol, cyclic or polycyclic aliphatic diols, particularly cyclohexanediol, norbornanediol, tricyclodecanediol and tricyclodecanedimethanol (octahydro-4,7-methano-1H-indenedimethanol). Dental materials, including, as described in any one of the preceding items. (Item 7) The dental material according to any one of the preceding items, comprising as component (d) at least one ABA and / or AB block copolymer, wherein the A block is an oligomer composed of one or more of the following monomers: cyclic aliphatic esters or ethers, arylene oxides, alkylene oxides, radical polymerizable monomers, such as α,β-unsaturated acids and α,β-unsaturated acid esters, and the B block is a polysiloxane oligomer and / or polyvinyl oligomer and / or polyalkene oligomer and / or polydiene oligomer. (Item 8) The dental material according to any one of the preceding items, comprising as component (d) at least one ABA and / or AB block copolymer, wherein the A block is an oligomer of polycaprolactone (PCL), poly(2,6-dimethyl-1,4-phenylene oxide), poly(ethylene oxide), poly(propylene oxide), or poly(meth)acrylate building block, and the B block is an oligomer of poly(dimethylsiloxane) (PDMS), poly(isoprene), poly(vinyl acetate), poly(isobutene), cis-poly(butadiene), or poly(ethylene) building block. (Item 9) The dental material according to any one of the preceding items, comprising as component (d) at least one ABA triblock copolymer of the PCL-b-PDMS-b-PCL and / or PMMA-b-PDMS-b-PMMA type having an A:B molar ratio of 0.1 to 5 and a molar mass of 3 to 25 kDa, preferably 4 to 20 kDa, and particularly preferably 5 to 10 kDa. (Item 10) Component (e) is preferably benzophenone, benzoin or its derivatives, α-diketone or its derivatives, such as 9,10-phenanthrenequinone, 1-phenyl-propane-1,2-dione, diacetyl or 4,4'-dichlorobenzyl, camphorquinone (CQ), 2,2-dimethoxy-2-phenylacetophenone, or an amine that is a reducing agent, such as 4-(dimethylamino)-benzoic acid ester (EDMAB), N,N-dimethylaminoethyl methacrylate, N,N-dimethyl-sym.-xylidine or α-diketone combined with triethanolamine, monoacyltrialkylgermanium, diacyldialkylgermanium, tetraacylgermanium, tetraacylstannane, benzoyltrimethylgermanium, dibenzoyldiethylgermanium, bis(4-methoxybenzoyl)diethylgermanium, tetrakis(2-methylbenzoyl)germane or tetrakis(mesitoyl)stannane or mixtures thereof. Norish type I photoinitiators such as acetophenone, e.g., 2,2-diethoxy-1-phenylethane; benzoin ether, e.g., Irgacure 651 (benzyldimethylketal); hydroxyalkylphenylacetophenone, e.g., Irgacure 184 (1-hydroxycyclohexylphenylketone); acylphosphine oxide or bisacylphosphine oxide, e.g., Irgacure TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide) or Irgacure 819 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide); 2-benzyl-2-(dimethylamino)-4'-morpholinylbutyrophenone (Irgacure 369) and / or 1-butanone-2-(dimethylamino)-2-(4-methylphenyl)methyl-1-4-(4-morpholinyl)phenyl (Irgacure 379). A dental material according to any one of the preceding items, comprising at least one photoinitiator selected from the above. (Item 11) In all cases, the composition is as follows, relative to the total mass of the aforementioned material: (a) 30-70% by weight, preferably 30-61% by weight, particularly preferably 40-60% by weight, at least one aromatic bicyclic or tricyclic mono(meth)acrylate, (b) 20-60% by weight, preferably 30-55% by weight, particularly preferably 33-55% by weight, of at least one urethane di(meth)acrylate telekel having a number average molar mass of 750-2000 g / mol, (c) 0 to 30% by weight, preferably 0 to 20% by weight, particularly preferably 0% by weight, di(meth)acrylate monomer(s) (d) 1 to 12% by weight, preferably 2 to 12% by weight, and particularly preferably 2 to 10% by weight, at least one ABA or AB block copolymer (e) 0.1 to 5.0% by weight, preferably 0.2 to 4.0% by weight, and particularly preferably 0.3 to 3.0% by weight, at least one initiator for radical polymerization, (f) Core-shell polymer particles in an amount of 0-15% by weight, preferably 0-5% by weight, and particularly preferably 0% by weight. (g) 0-20% by weight, preferably 0-15% by weight, particularly preferably 0-10% by weight of filler, (h) 0-1.0% by weight, preferably 0-0.7%, particularly preferably 0-0.5% by weight of an ultraviolet absorber, (i) 0 to 0.5% by weight, preferably 0 to 0.1% by weight, and particularly preferably 0 to 0.05% by weight of a fluorescent whitening agent, (j) 0-15% by weight, preferably 0-10% by weight, and especially preferably 0.2-5% by weight of further additives A dental material having the characteristics described in any one of the preceding items. (Item 12) In all cases, relative to the total mass of the aforementioned material, (a) 40-61% by weight of 2-phenoxyethyl (meth)acrylate, 2-(o-biphenyloxy)ethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-[(benzyloxycarbonyl)amino]ethyl (meth)acrylate, 1-phenoxypropan-2-yl (meth)acrylate, 2-(benzyloxy)-ethyl (meth)acrylate, 2-(methacryloyloxy)ethyl (meth)acrylate, 3-Phenoxybenzyl (meth)acrylate, phenoxypropyl (meth)acrylate, 2-benzyloxyethyl (meth)acrylate, 2-benzoyloxyethyl (meth)acrylate, 2-(meth)acryloyloxybenzoate methyl ester, 2-phenylethyl (meth)acrylate, tricyclodecane (meth)acrylate, tricyclodecane methyl (meth)acrylate and / or 2-(p-cumylphenoxy)ethyl methacrylate, (b) At least one urethane di(meth)acrylate telekel having a number average molar mass of 750 to 2000 g / mol and at least four urethane groups, prepared by reacting 1 mol of ethoxylated or propoxylated bisphenol A, decanediol or dodecanediol in 33 to 55% by weight with 2 mol of isophorone diisocyanate (IPDI), and then with 2 mol of 2-hydroxyethyl methacrylate (HEMA) or hydroxypropyl methacrylate (HPMA), (c) 0% by weight of further di(meth)acrylate monomers (d) At least one ABA or AB block copolymer comprising 2 to 10% by weight, wherein the A block is composed of oligomer polycaprolactone, poly(2,6-dimethyl-1,4-phenylene oxide), poly(ethylene oxide), poly(propylene oxide), or poly(meth)acrylate building blocks, and the B block is composed of poly(dimethylsiloxane), poly(isoprene), poly(vinyl acetate), poly(isobutene), cis-poly(butadiene), or poly(ethylene) building blocks, (e) 0% core-shell polymer, (f) 0.1 to 5.0% by weight of at least one photoinitiator, and (g) 0.2-5% by weight of one or more additional additives Dental materials, including, as described in any one of the preceding items. (Item 13) A dental material as described in any one of the preceding items, having a transparency of ≥60% and a viscosity of ≤10.0 Pa·s at 25°C. (Item 14) 300-5000 mol / m³ 3 A dental material having the crosslinking density after curing, as described in any one of the preceding items. (Item 15) A process for producing dental molded parts, (i) By directly or indirectly digitizing the tooth(s) to be restored using a computer, a virtual image of the tooth's condition is created. (ii) Next, based on this image, a model of the dental restoration or prosthesis is constructed on the computer, (iii) Next, the dental material described in any one of the preceding items is polymerized in layers by selective light irradiation for forming the dental restoration, (iv) Next, clean the workpiece by treating it with a solvent as necessary. (v) The workpiece is then further cured, if necessary, by irradiation with light and / or heating to a temperature above 50°C. process. (Item 16) Use of any of the preceding items as dental materials or for the creation or repair of dental molded parts. ((Item 17) Dental materials as described in any one of the preceding items, for the production or repair of dental molded parts. [Modes for carrying out the invention]

[0024] This disclosure provides a radically polymerizable dental material containing at least one ABA or AB block copolymer, preferably at least one monofunctional radical polymerizable monomer (a), and preferably at least one radically polymerizable urethane di(meth)acrylate telekel (b).

[0025] The dental material according to the present invention preferably has the following composition: (a) 30-70% by weight, preferably 30-61% by weight, particularly preferably 40-60% by weight, at least one aromatic bicyclic or tricyclic mono(meth)acrylate, (b) 20-60% by weight, preferably 30-55% by weight, particularly preferably 33-55% by weight, of at least one urethane di(meth)acrylate telekel having a number average molar mass of 750-2000 g / mol, (c) 0 to 30% by weight, preferably 0 to 20% by weight, particularly preferably 0% by weight, di(meth)acrylate monomer(s) (d) At least one ABA and / or AB block copolymer in an amount of 1 to 12% by weight, preferably 2 to 12% by weight, and particularly preferably 2 to 10% by weight, wherein the A block (or more) is homogeneously miscible with a mixture of components (a) to (c), and the B block is not homogeneously miscible with a mixture of components (a) to (c), and (e) 0.1 to 5.0% by weight, preferably 0.2 to 4.0% by weight, and particularly preferably 0.3 to 3.0% by weight, at least one initiator for radical polymerization. It has.

[0026] Unless otherwise stated, all weight percentages in this specification relate to the total mass of the material.

[0027] The dental material according to the present invention preferably comprises, as component (a), at least one aromatic bicyclic or tricyclic mono(meth)acrylate of formula (I). [ka] [In the formula, the variable elements have the following meanings: A is an aromatic group having 6 to 15 carbon atoms or a bicyclic or tricyclic aliphatic group having 7 to 10 carbon atoms, and A may be unsubstituted or substituted with one or more C1-C5 alkyl groups, C1-C5 alkoxy groups and / or chlorine atoms; R is either hydrogen or methyl; X 1 , X 2 These are mutually independent, neither present in any case, or are ether, ester, or urethane groups, and Y 1 X if it does not exist 1 Y does not exist. 2 X if it does not exist 2 It does not exist; Y 1 , Y2 These are branched or preferably linear aliphatic hydrocarbon radicals having 1 to 10 carbon atoms, which may be absent in either case or interrupted by 1 to 3 oxygen atoms. It contains.

[0028] In this specification, (meth)acrylate refers to acrylate, methacrylate, or a mixture thereof, and in any case preferably means methacrylate.

[0029] All formulas shown herein apply only to compounds that conform to the theory of chemical valence. The expression that a radical is interrupted by, for example, one or more oxygen atoms should be understood to mean that these atoms are inserted into the carbon chain of the radical in any case. Thus, these atoms are adjacent on both sides by C atoms and cannot be terminal. A C1 radical cannot branch or be interrupted. Corresponding to common nomenclature, aromatic hydrocarbon radicals also mean radicals containing aromatic and non-aromatic groups. A preferred aromatic radical is, for example, 2,2-diphenylpropane.

[0030] The preferred, particularly preferred, and extremely preferred definitions given to each variable element can be selected independently of each other in any case. Compounds in which all variable elements have preferred, particularly preferred, or extremely preferred definitions are, of course, particularly suitable according to the present invention.

[0031] Preferred aromatic group A is benzene, biphenyl, and 2,2-diphenylpropane. [ka]

[0032] Preferred bicyclic aliphatic group A are bicyclo[4.4.0]decane, bicyclo[4.3.0]nonane, bicyclo[2.2.2]octane, and bicyclo[2.2.1]heptane. [ka]

[0033] The preferred tricyclic aliphatic group A is tricyclo[5.2.1.0 2,6 It is a Deccan. [ka]

[0034] Preferred aromatic mono(meth)acrylates (a) are 2-phenoxyethyl (meth)acrylate, 2-(o-biphenyloxy)ethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-[(benzyloxycarbonyl)-amino]-ethyl (meth)acrylate, 2-[(benzylcarbamoyl)-oxy]-ethyl (meth)acrylate, 1-phenoxypropan-2-yl (meth)acrylate, and 2-(p-cumylphenoxy)-ethyl (meth)acrylate. Particularly preferred aromatic mono(meth)acrylates are 2-phenoxyethyl (meth)acrylate, 2-(o-biphenyloxy)ethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-[(benzyloxycarbonyl)amino]-ethyl (meth)acrylate, 1-phenoxypropan-2-yl (meth)acrylate, 2-(benzyloxy)ethyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, phenoxypropyl (meth)acrylate, 2-benzyloxyethyl (meth)acrylate, 2-benzoyloxyethyl (meth)acrylate, 2-(meth)acryloyloxybenzoate methyl ester, 2-phenylethyl (meth)acrylate and / or 2-(p-cumylphenoxy)ethyl (meth)acrylate.

[0035] Preferred bicyclic or tricyclic mono(meth)acrylates (a) are tricyclodecane(meth)acrylate, tricyclodecanemethyl(meth)acrylate, and especially 4,7,7-trimethylbicyclo[2.2.1]heptanyl(meth)acrylate. [ka]

[0036] The aromatic bicyclic or tricyclic monomethacrylates of formula (I) used in accordance with the present invention are characterized by good radical polymerizability. Furthermore, polymers of these monomethacrylates have relatively low polymerization shrinkage and good mechanical properties. The mono(meth)acrylates of formula (I) also have low volatility and relatively low viscosity due to their relatively high molar mass (150-350 g / mol) and relatively nonpolar structure.

[0037] The dental material according to the present invention contains, as component (b), at least one urethane dimethacrylate telekel having a molar mass of 750 to 2000 g / mol. Component (b) contains two radical polymerizable groups and therefore acts as a crosslinking agent during the polymerization of the material according to the present invention, i.e., leading to the formation of a polymer network. Due to the relatively high molar mass of component (b), a polymer with low network density and low polymerization shrinkage is obtained.

[0038] Unless otherwise stated, the molar mass of oligomers and polymers herein refers to the number-average molar mass, whose absolute value can be determined using known methods such as freezing point depression (freezing point depression method), boiling point elevation (boiling point elevation method), or vapor pressure reduction (vapor pressure osmotic method). The number-average molar mass of oligomers and polymers is preferably determined by gel permeation chromatography (GPC), a related method in which molecules are separated based on their size, and more specifically, on their hydrodynamic volume. The absolute molar mass is determined by calibration using known standard materials.

[0039] Urethane dimethacrylate telekel (b) is preferably obtained by reacting a diisocyanate with a diol (HO-DA-OH), and then reacting the α,ω-isocyanate-functionalized urethane telekel with HEMA or HPMA. DA is preferably an aromatic or aliphatic hydrocarbon radical having 6 to 33 carbon atoms, preferably a divalent polycyclic hydrocarbon radical, particularly o-diphenyl, p-diphenyl, or bisphenol A radical, or a branched or preferably linear C2-C2 radical. 18 This represents an alkylene group. A hydrocarbon radical may contain one or more oxygen atoms and / or sulfur atoms, with oxygen atoms being preferred.

[0040] Preferred diols of the formula HO-DA-OH include ethoxylated or propoxylated bisphenol A, o-diphenyl or p-diphenyl having 2 to 6 ethoxy or propoxy groups, and C2-C2 diols that can contain 1 to 4 O or S atoms in their carbon chain. 18 These are alkanediols. Particularly preferred diols are ethoxylated or propoxylated bisphenol A having 2, 3, or 4 ethoxy or propoxy groups, hexane-1,6-diol, octane-1,8-diol, nonane-1,9-diol, decane-1,10-diol, or dodecane-1,12-diol, tetra or pentaethylene glycol. Ethoxylated or propoxylated bisphenol A having 2 or 3 ethoxy or propoxy groups, decanediol, undecanediol, or dodecanediol, as well as cyclic or polycyclic aliphatic diols, particularly cyclohexanediol, norbornanediol, tricyclodecanediol, and tricyclodecanedimethanol (octahydro-4,7-methano-1H-indenedimethanol), are especially preferred.

[0041] Preferred diisocyanates include hexamethylene-1,6-diisocyanate (HMDI), 2,2,4-trimethylhexamethylene-1,6-diisocyanate (TMDI), 1-isocyanato-3-isocyanatomethyl-3,5,5-trimethylcyclohexane (isophorone diisocyanate, IPDI), m-tetramethylxylylene diisocyanate (1,3-bis(2-isocyanato-2-propyl)benzene, TMXDI), toluene-2,4-diisocyanate (TDI), diphenylmethane-4,4'-diisocyanate (MDI), and 1-isocyanato-4-[(4-isocyanatocyclohexyl)methyl]cyclohexane (H 12 MDI is preferred, and IPDI is particularly preferred.

[0042] According to the present invention, the telekel according to general formula (II) is preferred. [ka] [In the formula, the variable elements have the following meanings: R 1 , R 2 These are independent of each other and in each case are H or methyl, preferably methyl. R 3 , R 4 These are independent of each other and in each case are H or methyl, preferably methyl. x and y are independent of each other and are integers between 1 and 11, preferably between 1 and 5, in both cases. n is 1, 2, or 3, preferably 1. Z is [ka] Preferably [ka] And, DA is a structural element derived from the diol HO-DA-OH, formed by cleaving hydrogen atoms from two hydroxyl groups.

[0043] The preferred urethane dimethacrylate telekel according to the present invention is characterized by good radical polymerizability. Furthermore, this imparts good cohesive properties to the cured material.

[0044] Monofunctional methacrylate (a), urethane dimethacrylate telekel (b), and optionally another radical polymerizable monomer are preferably ν c = 300~5000 mol / m³ 3 Less than 400-3000 mol / m³ 3 It is used in proportions such that a crosslinked polymer having a network density is obtained. The crosslink density is substantially determined by the ratio of crosslinked monomers to monofunctional monomers. Dental materials in which the mole fraction of crosslinked monomers is in the range of 0.1 to 0.6, particularly preferably 0.15 to 0.45, are preferred according to the present invention. The mole fraction is calculated using all the radical polymerizable components of the material according to the present invention, i.e., components (a) to (c) in particular and, if necessary, another radical polymerizable monomer. Crosslinked monomer means all radical polymerizable components having two or more radical polymerizable groups, i.e., components (b) and (c) in particular. Crosslinked monomers are sometimes called polyfunctional monomers. Monofunctional monomers are monomers having only one radical polymerizable group.

[0045] The mesh density corresponds to the number of nodes per volume unit (in moles) and can be calculated from the plateau value of the storage modulus G' in the elastic region through dynamic mechanical measurements. Glass transition temperature T g and mesh density ν c This is determined using a rheometer, preferably an Anton Paar MCR301 rheometer. For this purpose, the storage and loss modulus of the test specimen (25 × 5 × 1 mm, clamped longitudinally) is measured between 25°C and 250°C (frequency 1 Hz, deformation 0.05%, heating rate 2 K / min). g This is the maximum value of the loss coefficient tan δ (the ratio of the loss modulus to the storage modulus). The mesh density is given by equation ν c =G' / (RT)(where G' is the temperature T) gThis is the storage modulus at +50K, where R is the general gas constant and T is T g It is calculated according to the temperature (in Kelvin) at +50K.

[0046] To further set the crosslinking density of the polymer and influence its mechanical properties, the dental material according to the present invention may additionally contain another di(meth)acrylate monomer (c) in addition to components (a) and (b).

[0047] Preferred di(meth)acrylate(c) is bisphenol A dimethacrylate (bis-GMA, an addition product of methacrylic acid and bisphenol A diglycidyl ether), ethoxylated or propoxylated bisphenol A dimethacrylate such as bisphenol A dimethacrylate SR-348c (Sartomer) having three ethoxy groups, 2,2-bis[4-(2-methacryloxypropoxy)phenyl]propane (UDMA, an addition product of HEMA and TMDI), V380 (an addition product of a mixture of 0.7 mol of 2-hydroxyethyl methacrylate and 0.3 mol of 2-hydroxypropyl methacrylate and 1 mol of α,α,α',α'-tetramethyl-m-xylylenediisocyanate), bis(methacryloyloxymethyl)tricyclo-[5.2.1.0 2,6 These include decane (DCP), di, tri, or tetraethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetra(meth)acrylate, as well as glycerol dimethacrylate and glycerol trimethacrylate, 1,4-butanediol dimethacrylate, 1,10-decanediol dimethacrylate (D3MA), and 1,12-dodecanediol dimethacrylate.

[0048] The di(meth)acrylate monomer (c) is characterized by a relatively low molar weight. Di(meth)acrylate (c) having a molar weight in the range of 200 to 800 g / mol, preferably 220 to 650 g / mol, is preferred according to the present invention. Due to its lower molar weight compared to urethane di(meth)acrylate telekel (b), di(meth)acrylate monomer (c) results in relatively strong crosslinking of the polymer, thus leading to a high network density, which may have an unfavorable effect on fracture toughness. Therefore, the proportion of another di(meth)acrylate is limited to a maximum of 30% by weight, preferably a maximum of 10% by weight. According to a particularly preferred embodiment, the dental material according to the present invention exclusively contains urethane di(meth)acrylate telekel (b) as a crosslinking agent.

[0049] Furthermore, the dental material according to the present invention may contain another mono(meth)acrylate in addition to component (a). The proportion of the other mono(meth)acrylate is preferably less than 10% by weight, and a material that does not contain the other mono(meth)acrylate is particularly preferred.

[0050] The dental material according to the present invention contains, as component (d), at least one ABA and / or one AB block copolymer. A block copolymer means a polymer consisting of two or more homopolymer blocks that are covalently bonded to each other.

[0051] The preferred block copolymers according to the present invention can be prepared using known methods of living polymerization or controlled polymerization, for example, by radical polymerization or ionic (anionic and cationic) polymerization, with controlled radical polymerization and living anionic polymerization being preferred. However, block copolymers can also be obtained by coupling the terminal groups of homopolymers. The block copolymers used according to the present invention can exist as diblock copolymers and triblock copolymers.

[0052] AB block copolymers can be prepared, for example, by coupling an A block having terminal OH groups with a B block having COOH groups through esterification. Terminal-functionalized homopolymer blocks can be prepared relatively easily using controlled radical polymerization methods or, in the case of anionic polymerization, by end capping.

[0053] For example, monomer A is anionically polymerized, and the OH group is inserted by end-capping. The OH terminal group can then be esterified with, for example, α-bromoisobutyric acid. The bromine terminal group obtained in the above process then serves as a starting point for the formation of block B through ATRP (atomic transfer radical polymerization) of monomer B initiated by a metal complex of, for example, Cu(I), Ru(I), or Fe(II).

[0054] Triblock copolymers can be prepared in a similar manner. For example, block B is prepared by the anionic polymerization of monomer B via a dianionic mechanism. The resulting B intermediate block has anionic terminal groups on each side and initiates the anionic polymerization of monomer A, forming two A blocks (Method 1). In either case, an ABA triblock copolymer is obtained by esterifying a telechelic B block having suitable functional groups, such as OH groups, at both ends with two A blocks, each functionalized on one side, for example, with a COOH group (Method 2). Finally, the OH-telechelic homopolymer of monomer B can be esterified with α-bromoisobutyric acid. The two bromine terminal groups thus formed in homopolymer block B can then be used as starting points for the formation of two A blocks by ATRP (Method 3).

[0055] During the synthesis of block copolymers, terminal or pendant-type polymerizable methacrylate groups can also be inserted. This results in better integration of the block copolymer into the polymer network formed by the radical copolymerization of the methacrylate groups.

[0056] The monomers are preferably selected such that block A is miscible with the resin matrix, i.e., the mixture of components (a) to (c), while block B is not miscible with the resin matrix.

[0057] Here, miscibility is described in a thermodynamic sense with respect to the single-phase state. According to this, a miscible polymer block means a polymer block composed of monomers, and its homopolymer is soluble in the resin matrix, and as a result the mixture has at least 95% clarity. In contrast, if the mixture is cloudy or opaque, i.e., if the clarity is less than 95%, the homopolymer, and therefore the corresponding polymer block, is not miscible with the resin matrix. Clarity is measured in transmission (D65) according to ISO 10526:1999 standard, using a spectrophotometer, e.g., a Konika-Minolta CM-5 spectrophotometer, on a 1 mm thick test specimen polished to high gloss.

[0058] Block copolymers significantly improve the fracture toughness of the material according to the present invention after curing. It is believed that the immismiability between the B block of the block copolymer and the remaining components of the composition according to the present invention leads to microphase separation, thus forming nanoscale morphologies. Here, the polymer of the ABA or AB block copolymer forms spherical or worm-like phases by self-assembly in the monomer resin or during curing, and these phases can interact with the crack tip; that is, the crack tip encounters a phase, and the fracture energy is distributed into the phase such that the crack does not move further through the material and its size does not increase. Crack growth can be observed in transparent materials under an electron microscope. In fracture mechanics, the foremost part of a crack is called the crack tip.

[0059] Preferred block copolymers according to the present invention are AB diblock and ABA triblock copolymers.

[0060] Block A is a polymer, preferably an oligomer, composed of one or more of the following monomers: cyclic aliphatic esters or ethers, arylene oxides, alkylene oxides, radical polymerizable monomers, such as α,β-unsaturated acids and α,β-unsaturated acid esters. Block A is preferably a poly(meth)acrylate oligomer, polylactone oligomer, phenylene oxide oligomer, or polyalkylene oxide oligomer. Most preferably, Block A is a polymer of caprolactone, 2,6-dialkyl-1,4-phenylene oxide, particularly 2,6-dimethyl-1,4-phenylene oxide, ethylene oxide, propylene oxide, or (meth)acrylate. Therefore, Block A is preferably a polycaprolactone (PCL) oligomer, a poly(2,6-dimethyl-1,4-phenylene oxide) oligomer, a poly(ethylene oxide) oligomer, a poly(propylene oxide) oligomer, or a poly(meth)acrylate oligomer.

[0061] Block B is preferably a polysiloxane oligomer and / or a polyvinyl oligomer and / or a polyalkene oligomer and / or a polydiene oligomer. Particularly preferably, Block B is a polydiene oligomer, a polyvinyl alkanoate oligomer or a polydiene oligomer of formula -O-(SiR 5 2-0) p - is a polysiloxane oligomer by [in the formula, R 5 is a linear C1-C 20 Alkyl, branched C3-C 12 Alkyl or C6-C 20 It is an aryl group, and each R 5 Radicals can be the same or different. p is a number between 3 and 100, preferably between 10 and 50.

[0062] Most preferably, block B is a polymer of dimethylchlorosilane, cyclotri or cyclotetradimethoxysilane, isoprene, vinyl acetate, isobutene, cis-butadiene, or ethylene. Therefore, block B is preferably a poly(dimethylsiloxane) (PDMS) oligomer, poly(isoprene) oligomer, poly(vinyl acetate) oligomer, poly(isobutene) oligomer, cis-poly(butadiene) oligomer, or poly(ethylene) oligomer.

[0063] Block B is characterized by relatively high flexibility. A flexible block refers to a block formed from monomers, the homopolymer of which has a glass transition temperature T of less than 50°C, preferably less than 0°C, and very preferably in the range of -30 to -110°C. G The block copolymer having flexible blocks improves fracture toughness, but does not impair the polymer's flexural strength and modulus as much as internal plasticizers do.

[0064] According to the present invention, polyester-polysiloxane block copolymers represented by the following general formula are preferred: (PCL) q -b-(PDMS) r -b-(PCL) q [In the formula, In all cases, q is a number between 5 and 40, preferably between 10 and 20. r is a number between 10 and 100, preferably between 30 and 60.

[0065] (PCL) q (PDMS) represents a polycaprolactone composed of q caprolactone monomers. r The letter 'b' represents poly(dimethylsiloxane), which is composed of r dimethylsiloxane monomers. The letter 'b' represents a block.

[0066] A poly(meth)acrylate-polysiloxane block copolymer containing a polymethyl methacrylate radical as block A and a polysiloxane radical as block B, wherein the polysiloxane radical is preferably as defined above, and most preferably a poly(dimethylsiloxane) radical, is even more preferable.

[0067] Particularly preferred are the ABA triblock copolymers PCL-b-PDMS-b-PCL and PMMA-b-PDMS-b-PMMA, with a molar ratio A:B of 0.1 to 5, and a molar mass of preferably 3 to 25 kDa, particularly preferably 4 to 20 kDa, and most particularly preferably 5 to 10 kDa. The preferred block copolymer is PCL-b-PDMS-b-PCL, where the PDMS block has a molar mass of about 3200 g / mol, and the PCL block has a molar mass of about 1600 g / mol in either case. PCL represents polycaprolactone, PDMS represents poly(dimethylsiloxane), and PMMA represents polymethyl methacrylate.

[0068] The block copolymer(s) are used in an amount of preferably 1 to 12% by weight, particularly preferably 2 to 10% by weight, and most preferably 3 to 8% by weight, relative to the total weight of the dental material.

[0069] The block copolymers used according to the present invention have been found to significantly improve the fracture toughness of the polymer network without compromising transparency. Furthermore, they exhibit only a relatively slight increase in viscosity. Another advantage of the block copolymers used according to the present invention is that they can be easily and homogeneously mixed with the remaining components of the material, whereas homogeneous dispersion of core-shell polymer particles is far more complex. Moreover, the particles tend to settle, and as a result, compositions based on core-shell particles are unstable. On the other hand, block copolymers can be readily incorporated into resin mixtures, and as a result, the material can be adapted to the intended application, setting the desired fracture toughness and fracture work without any problems.

[0070] The dental material according to the present invention contains, as component (e), at least one initiator for radical polymerization, preferably a photoinitiator.

[0071] Preferred photoinitiators include benzophenone, benzoin and their derivatives, as well as α-diketones and their derivatives, such as 9,10-phenanthrenequinone, 1-phenyl-propane-1,2-dione, diacetyl, or 4,4'-dichlorobenzyl. Camphorquinone (CQ) and 2,2-dimethoxy-2-phenylacetophenone are particularly preferred, and α-diketones combined with reducing agents such as amines, such as 4-(dimethylamino)benzoate (EDMAB), N,N-dimethylaminoethyl methacrylate, N,N-dimethyl-sym.-xylidine, or triethanolamine are most particularly preferred. Preferred monomolecular photoinitiators in the visible range include monoacyltrialkylgermanium, diacyldialkylgermanium, and tetraacylgermanium, as well as tetraacyl stannanes, such as benzoyltrimethylgermanium, dibenzoyldiethylgermanium, bis(4-methoxybenzoyl)-diethylgermanium, tetrakis(2-methylbenzoyl)germane, or tetrakis(mesitoyl)stannane. Mixtures of different photoinitiators can also be used, for example, bis(4-methoxybenzoyl)diethylgermanium combined with camphorquinone and ethyl 4-dimethylaminobenzoate.

[0072] Preferred initiators for curing the dental material according to the present invention with UV light are Norish type I photoinitiators, particularly acetophenone, e.g., 2,2-diethoxy-1-phenylethane; benzoin ether, e.g., Irgacure 651 (benzyldimethyl ketal); hydroxyalkylphenylacetophenone, e.g., Irgacure 184 (1-hydroxycyclohexylphenyl ketone); acylphosphine oxide or bisacylphosphine oxide, e.g., Irgacure TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide) and Irgacure 819 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide). Further preferred photoinitiators are 2-benzyl-2-(dimethylamino)-4'-morpholinbutyrophenone (Irgacure 369) and 1-butanone-2-(dimethylamino)-2-(4-methylphenyl)methyl-1-4-(4-morpholinyl)phenyl (Irgacure 379). Particularly preferred photoinitiators are bis(4-methoxybenzoyl)diethylgermanium, Irgacure TPO, and Irgacure 819, as well as camphorquinone / 4-(dimethylamino)benzoate. In post-tempering, it is advantageous to use two photoinitiators with different absorption ranges, such as Irgacure TPO and camphorquinone / 4-(dimethylamino)benzoate.

[0073] The dental materials according to the present invention may also contain, as an alternative or additional, a thermal initiator, such as an azo compound like 2,2'-azobis(isobutyronitrile) (AIBN) or azobis-(4-cyanovaleric acid), or a peroxide such as dibenzoyl peroxide, dilauroyl peroxide, tert-butyl peroctoate, tert-butyl perbenzoate, or di-(tert-butyl) peroxide. Combinations with aromatic amines may also be used to promote peroxide-mediated initiation. Preferred redox systems are combinations of dibenzoyl peroxide with amines such as N,N-dimethyl-p-toluidine, N,N-dihydroxyethyl-p-toluidine, ethyl p-dimethylaminobenzoate, or structurally related systems.

[0074] The initiator(s) are used in a total amount of preferably 0.1 to 5.0% by weight, particularly preferably 0.2 to 4% by weight, and most particularly preferably 0.3 to 3.0% by weight, and these amounts include all initiator components, such as reducing agents.

[0075] To further improve fracture toughness and impact resistance, the dental material according to the present invention may also contain a certain proportion of one or more core-shell polymers (component (f)). For example, a core-shell polymer (CSP) having a soft polymer core made of cross-linked butyl acrylate and a somewhat hard polymer shell, such as PMMA, is preferred. The soft or flexible polymer has a glass transition temperature T of less than 50°C, preferably less than 0°C, and very preferably in the range of -30 to -110°C. G This refers to a polymer having [a certain characteristic]. At approximately -110°C, T G PDMS having the following characteristics is a preferred example. A rigid polymer means a polymer having a glass transition temperature of over 50°C, preferably over 80°C. G PMMA having the following characteristics is a preferred example.

[0076] The fracture toughness improvement effect of CSP particles in a radical dimethacrylate polymer network depends, in particular, on the type, particle size, crosslinking density, and weight ratio of the core to the shell of the CSP particles, preferably in the range of 1:1 to 200:1. The crosslinking density is substantially determined by the proportion of crosslinking monomers in the particle core, which is preferably in the range of 1 to 10% by weight relative to the mass of the core. Particles having a particle size of 0.20 to 5.0 μm are preferred according to the present invention.

[0077] According to the present invention, CSP particles having a core made of a soft plastic such as polybutadiene, polyisoprene, polybutyl acrylate, MMA-butadiene-styrene copolymer (MBS), or polydimethylsiloxane, and a shell made of a hard plastic such as PMMA or MMA-styrene copolymer, are preferred. Suitable CSP particles according to the present invention are commercially available from, for example, Arkema (Clearstrength), Soken Chemical (Chemisnow), or Kaneka (e.g., M521 or M210).

[0078] Core-shell polymers can be added in amounts up to 15% by weight. The disadvantages of using core-shell polymers are that they can significantly impair the transparency of the composition, negatively affect the curing depth in the case of photopolymerization, and additionally have negative aesthetic effects in the case of dental molded articles. Therefore, according to the present invention, materials containing at most 5% by weight of core-shell particles, and particularly preferably no core-shell particles, are preferred. Incorporating CSP particles into dental materials ensures good dispersion.

[0079] To influence its mechanical properties, the dental material according to the present invention can be reinforced with an inorganic granular filler (g).

[0080] Preferred inorganic fillers include oxides such as SiO2, ZrO2 and TiO2 or mixed oxides of SiO2, ZrO2, ZnO and / or TiO2; nano-granular or micro-fine fillers such as fumed silica or precipitated silica; quartz, glass ceramics, borosilicate or radiopaque glass powders, preferably glass powders such as barium or strontium aluminum silicate glass; and radiopaque fillers such as ytterbium trifluoride, tantalum(V) oxide, barium sulfate, or mixed oxides of SiO2 and ytterbium(III) oxide or tantalum(V) oxide. The dental material according to the present invention may further contain fibrous fillers, nanofibers, whiskers, or mixtures thereof. According to a preferred embodiment, the material according to the present invention does not contain fluoroaluminosilicate glass, calcium aluminum silicate glass, or other fillers that react with organic acids in the sense of an acid-base reaction.

[0081] Preferably, the oxide has a particle size of 0.010 to 15 μm, the nano-granular or micro-fine filler has a particle size of 10 to 300 nm, the glass powder has a particle size of 0.01 to 15 μm, preferably 0.2 to 1.5 μm, and the radiopaque filler has a particle size of 0.2 to 5 μm.

[0082] Particularly preferred fillers are mixed oxides of SiO2 and ZrO2 having a particle size of 10 to 300 nm, glass powders having a particle size of 0.2 to 1.5 μm, especially radiopaque glass powders such as barium or strontium aluminum silicate glass, and radiopaque fillers having a particle size of 0.2 to 5 μm, especially ytterbium trifluoride and / or mixed oxides of SiO2 and ytterbium(III) oxide.

[0083] To improve the bonding between filler particles and the crosslinked polymerization matrix, SiO2-based fillers can be surface-modified with methacrylate-functionalized silanes. A preferred example of such silane is 3-methacryloyloxypropyl-trimethoxysilane. For surface modification of non-silicate fillers such as ZrO2 or TiO2, functionalized acidic phosphates such as 10-methacryloyloxydecyldihydrogen phosphate can also be used.

[0084] Further preferred fillers include granular wax, particularly carnauba wax, having a particle size of 1 to 10 μm; uncrosslinked or partially crosslinked polymethyl methacrylate (PMMA) particles, having a particle size of 500 nm to 10 μm; and polyamide-12 particles, having a particle size of 5 to 10 μm.

[0085] Furthermore, the dental material according to the present invention may contain so-called prepolymer fillers or isofillers, i.e., pulverized composites having a broad particle size distribution, for example, 0.05 to 20 μm, and particularly about 0.1 to about 10 μm. The prepolymer fillers or isofillers are preferably surface-modified, and particularly silane-treated.

[0086] Unless otherwise stated, all particle sizes in this specification are weight-average particle sizes. Particle size determination in the range of 0.1 μm to 1000 μm is performed by static light scattering, preferably using an LA-960 static laser scattering particle size analyzer (Horiba, Ltd., Japan). Here, a laser diode with a wavelength of 655 nm and an LED with a wavelength of 405 nm are used as light sources. The use of two light sources with different wavelengths makes it possible to measure the entire particle size distribution of the sample in just one measurement trial, and the measurement is performed as a wet measurement. For this purpose, an aqueous dispersion of 0.1 to 0.5% of the filler is prepared, and its scattered light is measured in a flow cell. Scattered light analysis for calculating particle size and particle size distribution is performed according to DIN / ISO 13320 following Mie theory.

[0087] Particle sizes smaller than 0.1 μm are preferably determined by dynamic light scattering (DLS). Particle size measurements in the range of 5 nm to 0.1 μm are preferably performed by dynamic light scattering (DLS) of an aqueous particle dispersion, preferably using a Malvern Zetasizer Nano ZS (Malvern Instruments, Malvern UK), with a wavelength of 633 nm and a He-Ne laser, at a scattering angle of 90° and 25°C.

[0088] Light scattering decreases as particle size decreases. Particle sizes smaller than 0.1 μm can also be determined by SEM or TEM spectroscopy. Transmission electron microscopy (TEM) is preferably performed using a Philips CM30 TEM with an accelerating voltage of 300 kV. For sample preparation, droplets of the particle dispersion are applied to a 50 Å thick copper grid (mesh size 300) coated with carbon, and then the solvent is evaporated.

[0089] Fillers are classified into macrofillers and microfillers according to their particle size. Fillers with an average particle size of 0.2 to 10 μm are called macrofillers, and fillers with an average particle size of about 5 to 100 nm are called microfillers. For example, macrofillers are obtained by crushing materials such as quartz, radiopaque glass, borosilicate, or ceramics, and usually consist of brittle parts. Fumed SiO2 or precipitated silica, or mixed oxides obtained by hydrolysis cocondensation of metal alkoxides, such as SiO2-ZrO2, are preferably used as microfillers. Microfillers preferably have an average particle size of about 5 to 100 nm. Fillers with smaller particle sizes have a greater thickening effect.

[0090] In preferred embodiments, the dental material according to the present invention contains two or more fillers, particularly a mixture of two or more fillers having different particle sizes. It has been found that the viscosity of the material does not increase excessively by the use of such a mixture of fillers, and therefore the composition can be easily processed using additive processes, such as stereolithography. The total filler content is preferably in the range of 0 to 20% by weight, and particularly preferably in the range of 0 to 10% by weight.

[0091] The dental material according to the present invention may further contain one or more types of ultraviolet absorbers (h). The ultraviolet absorbers reduce the light penetration depth, and consequently the polymerization depth, during the photo-induced curing of the composition according to the present invention. This is particularly advantageous for stereolithographic applications, as only thin layers can be cured by stereolithography. The use of ultraviolet absorbers can improve accuracy in the stereolithographic process.

[0092] UV absorbers based on benzotriazole, benzophenone, or triazine are preferred. Particularly preferred UV absorbers are 2,2'-methylenebis[6-(2H-benzotriazole-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol], 2,2',4,4'-tetrahydroxybenzophenone, 2-tert-butyl-6-(5-chloro-2H-benzotriazole-2-yl)-4-methylphenol (bumetrizole), 2,2'-benzene-1,4-diylbis(4H-3,1-benzoxazine-4-one), and 2-(4,6-bis-(2,4-dimethylphenyl)-1,3,5 These are triazine-2-yl)-5-(octyloxy)-phenol, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxyphenyl)benzotriazole, 2-(2H-benzotriazol-2-yl)-6-dodecyl-4-methylphenol, 2'-hydroxy-3',5'-di-t-butylphenyl)-5-chlorobenzotriazole, 2,2'-dihydroxy-4-methoxybenzophenone, and 2,2'-dihydroxy-4,4'-dimethoxybenzophenone. So-called hindered amine light stabilizers such as bis(1,2,2,6,6-pentamethyl-4-piperidyl) sebacate, methyl-1,2,2,6,6-pentamethyl-4-piperidyl sebacate, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, and bis(1,2,2,6,6-pentamethyl-4-piperidyl)-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate are even more preferred. Particularly preferred ultraviolet absorbers are bumetrizole and 2,2',4,4'-tetrahydroxybenzophenone.

[0093] The UV absorber preferably has an absorption maximum corresponding to the wavelength of light used for curing. UV absorbers having an absorption maximum in the range of 320 to 500 nm, preferably 380 to 480 nm, are advantageous, and UV absorbers having an absorption maximum of less than 400 nm are particularly preferred.

[0094] UV absorbers are used as needed, preferably in an amount of 0-1.0% by weight, and particularly preferably 0.01-0.5% by weight. Bumetrizole is used, preferably in an amount of 0.01-0.2% by weight, and particularly preferably 0.02-0.15% by weight, and 2,2',4,4'-tetrahydroxybenzophenone is used, preferably in an amount of 0.01-0.07% by weight. All data relate to the total weight of the material. Dental materials that do not contain UV absorbers are preferred.

[0095] The dental material according to the present invention may also contain one or more fluorescent whitening agents (i). Fluorescent whitening agents that absorb light in the UV range, i.e., light with wavelengths less than 400 nm, are preferred according to the present invention. The addition of a fluorescent whitening agent can reduce the light penetration depth and, consequently, the curing depth, thereby increasing the accuracy in the stereolithographic process. Fluorescent whitening agents that can re-emit light absorbed in the UV range as light with wavelengths of 400-450 nm are particularly preferred. Such fluorescent whitening agents increase the reactivity of the material because, for their fluorescence, they emit the absorbed short-wave light as longer-wave blue light, thus providing additional luminosity power for photoinitiation. Preferred fluorescent whitening agents according to the present invention are 2,5-bis(5-tert-butyl-benzoxazole-2-yl)thiophene and fluorescent agents in the form of terephthalic acid derivatives such as 2,5-dihydroxyterephthalate diethyl ester or diethyl-2,5-dihydroxyterephthalate.

[0096] In all cases, the fluorescent whitening agent(s)(s)(s)(s)(s)(s)(s)) are used as needed, preferably in an amount of 0-0.1% by weight, particularly preferably 0.001-0.05% by weight, and most particularly preferably 0.002-0.02% by weight relative to the total weight of the material. Dental materials that do not contain fluorescent whitening agents are preferred.

[0097] Fluorescent whitening agents can be used in combination with ultraviolet absorbers. In this case, the weight ratio of the ultraviolet absorber to the fluorescent whitening agent is preferably in the range of 2:1 to 50:1, particularly preferably 2:1 to 30:1, and most preferably 2:1 to 5:1 or 10:1 to 25:1. A combination containing 2,2',4,4'-tetrahydroxybenzophenone or bumetrizole as the ultraviolet absorber and 2,5-bis(5-tert-butyl-benzoxazole-2-yl)thiophene as the fluorescent whitening agent is preferred. A combination of 2,2',4,4'-tetrahydroxybenzophenone and 2,5-bis(5-tert-butyl-benzoxazole-2-yl)thiophene in a weight ratio of 2:1 to 10:1, preferably 2:1 to 5:1, or a combination of bumetrizole and 2,5-bis(5-tert-butyl-benzoxazole-2-yl)thiophene in a weight ratio of 5:1 to 30:1, preferably 10:1 to 20:1, is extremely preferred.

[0098] The dental material according to the present invention may additionally contain other additives (j), in particular stabilizers, colorants, plasticizers, thixotropic additives, microbial active ingredients and / or foaming agents.

[0099] The dental material according to the present invention preferably contains one or more stabilizers. These are free radical scavenging substances that prevent premature polyreactions. Stabilizers are also called polymerization inhibitors. Inhibitors or stabilizers improve the storage stability of the material.

[0100] Preferred inhibitors are phenols such as hydroquinone monomethyl ether (MEHQ) or 2,6-di-tert-butyl-4-methylphenol (BHT). The phenol is preferably used at a concentration of 0.001–0.50% by weight. Even more preferred inhibitors are phenothiazine, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical, galbinoxyl radical, triphenylmethyl radical, and 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) radical. These inhibitors are preferably used in amounts of 0.001–0.02% by weight. Polymerization does not occur until these additives are exhausted. The amounts in any case are related to the total mass of the material. Preferably, a mixture of inhibitors containing at least one phenol and at least one further initiator is used.

[0101] Furthermore, the dental material according to the present invention may also contain a coloring agent, preferably at a concentration of 0.0001 to 0.5% by weight. The coloring agent is used primarily for aesthetic purposes. Preferred coloring agents according to the present invention are organic dyes and pigments, particularly azo dyes, carbonyl dyes, cyanine dyes, azomethine and methine, phthalocyanine and dioxazine. Dyes soluble in the material according to the present invention, particularly azo dyes, are especially preferred. Furthermore, inorganic pigments and particularly organic pigments that can be sufficiently dispersed in the dental material according to the present invention are suitable as coloring agents. Preferred inorganic pigments are metal oxides or hydroxides, such as titanium dioxide or ZnO as a white pigment, iron oxide (Fe2O3) as a red pigment, or iron hydroxide (FeOOH) as a yellow pigment. Preferred organic pigments are azo pigments such as monoazo yellow and orange pigments, diazo pigments, or β-naphthol pigments, as well as non-azo or polycyclic pigments such as phthalocyanine, quinacridone, perylene and flavanthron pigments. Azo pigments and non-azo pigments are particularly preferred.

[0102] Furthermore, the dental material according to the present invention may contain one or more plasticizers. The plasticizer prevents the polymer from becoming brittle after photochemical curing and possible drying. In addition, the plasticizer ensures sufficient flexibility. The plasticizer is preferably added at a concentration of 0.2 to 5% by weight. Preferred plasticizers are phthalates such as dibutyl phthalate or dihexyl phthalate, non-acidic phosphates such as tributyl phosphate or tricresyl, n-octanol, glycerol, or polyethylene glycol. Tartrate esters or citrate esters such as triestrate, characterized by good biocompatibility, are particularly preferred.

[0103] The dental material according to the present invention may further contain one or more thixotropic additives. These additives increase the viscosity of the material and therefore can prevent, for example, the settling of the filler. In particular, materials containing a filler preferably contain at least one thixotropic additive. Preferred thixotropic additives are polymers containing OH groups, such as cellulose derivatives, and inorganic substances, such as layered silicates. In order not to increase the viscosity of the material too much, the dental material according to the present invention preferably contains only 0 to 3.0% by weight, particularly preferably 0 to 2.0% by weight, and most preferably 0.1 to 2.0% by weight of the thixotropic additive based on the total weight of the material.

[0104] For example, highly dispersible SiO2, i.e., small primary particle size (<20 nm) and large surface area (>100 m²). 2 Certain packing materials, such as SiO2, which have the properties of ), also exhibit a thixotropic effect. Such packing materials can be replaced by thixotropic additives.

[0105] The rheological properties of the dental materials according to the present invention are adapted to the desired target application. Materials for stereolithographic processing are preferably adjusted so that their viscosity is in the range of 50 mPa·s to 100 Pa·s, preferably 100 mPa·s to 10 Pa·s, and particularly preferably 100 mPa·s to 5 Pa·s. Viscosity is determined at 25°C using a cone-plate viscometer (shear rate 100 / sec). Dental materials according to the present invention have a viscosity of particularly preferably <10 Pa·s, and very particularly preferably <5 Pa·s, at 25°C. Viscosity is preferably determined using an Anton Paar MCR 302 viscometer with a CP25-2 cone-plate measuring system, with a measurement gap of 53 μm during rotation at a shear rate of 100 / sec. Due to their low viscosity, dental materials according to the present invention are particularly suitable for processing using additive manufacturing processes, such as 3D printing or stereolithography. The processing temperature is preferably in the range of 10 to 70°C, and particularly preferably in the range of 20 to 30°C.

[0106] According to the present invention, dental materials having the following composition are particularly preferred. (a) 30-70% by weight, preferably 30-61% by weight, particularly preferably 40-60% by weight, at least one aromatic bicyclic or tricyclic mono(meth)acrylate, (b) 20-60% by weight, preferably 30-55% by weight, particularly preferably 33-55% by weight, of at least one urethane di(meth)acrylate telekel having a number average molar mass of 750-2000 g / mol, (c) 0 to 30% by weight, preferably 0 to 20% by weight, particularly preferably 0% by weight, di(meth)acrylate monomer(s), (d) 1 to 12% by weight, preferably 2 to 12% by weight, and particularly preferably 2 to 10% by weight, at least one ABA or AB block copolymer (e) 0.1 to 5.0% by weight, preferably 0.2 to 4.0% by weight, and particularly preferably 0.3 to 3.0% by weight, at least one initiator for radical polymerization, (f) Core-shell polymer particles in an amount of 0-15% by weight, preferably 0-5% by weight, and particularly preferably 0% by weight. (g) 0-20% by weight, preferably 0-15% by weight, particularly preferably 0-10% by weight of filler, (h) 0-1.0% by weight, preferably 0-0.7% by weight, particularly preferably 0-0.5% by weight of an ultraviolet absorber, (i) 0 to 0.5% by weight, preferably 0 to 0.1% by weight, and particularly preferably 0 to 0.05% by weight of a fluorescent whitening agent, (j) A further additive in an amount of 0-15% by weight, preferably 0-10% by weight, and especially preferably 0.05-5% by weight.

[0107] Dental materials having the following composition are extremely preferred. (a) 30-70% by weight, preferably 30-61% by weight, particularly preferably 40-60% by weight, at least one mono(meth)acrylate of formula (I), (b) 20-60% by weight, preferably 30-55% by weight, particularly preferably 33-55% by weight, of at least one urethane di[meth]acrylate terekel of formula (II), (c) 0 to 30% by weight, preferably 0 to 20% by weight, particularly preferably 0% by weight, further di(meth)acrylate monomer (d) 2 to 12% by weight, preferably 2 to 10% by weight, and particularly preferably 3 to 8% by weight, at least one ABA or AB block copolymer (e) At least one photoinitiator in an amount of 0.1 to 5.0% by weight, preferably 0.2 to 4% by weight, and particularly preferably 0.3 to 3.0% by weight, (f) Core-shell polymer particles in an amount of 0-15% by weight, preferably 0-5% by weight, and particularly preferably 0% by weight. (g) 0-20% by weight, preferably 0-15% by weight, particularly preferably 0-10% by weight of filler, (h) 0-1.0% by weight, preferably 0-0.7%, particularly preferably 0-0.5% by weight of an ultraviolet absorber, (i) 0 to 0.5% by weight, preferably 0 to 0.1% by weight, and particularly preferably 0 to 0.05% by weight of a fluorescent whitening agent, (j) A further additive in an amount of 0-15% by weight, preferably 0-10% by weight, and especially preferably 0.02-5% by weight.

[0108] Unless otherwise stated, all weight percentages in this specification relate to the total mass of dental materials.

[0109] (a) 40-61% by weight of 2-phenoxyethyl (meth)acrylate, 2-(o-biphenyloxy)ethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-[(benzyloxycarbonyl)amino]ethyl (meth)acrylate, 1-phenoxypropan-2-yl (meth)acrylate, 2-(benzyloxy)-ethyl (meth)acrylate, 2-(methacryloyloxy)ethyl (meth)acrylate, 3-Phenoxybenzyl (meth)acrylate, phenoxypropyl (meth)acrylate, 2-benzyloxyethyl (meth)acrylate, 2-benzoyloxyethyl (meth)acrylate, 2-(meth)acryloyloxybenzoate methyl ester, 2-phenylethyl (meth)acrylate, tricyclodecane (meth)acrylate, tricyclodecane methyl (meth)acrylate and / or 2-(p-cumylphenoxy)ethyl methacrylate, (b) At least one urethane di(meth)acrylate telekel having a number average molar mass of 750 to 2000 g / mol and at least four urethane groups, prepared by reacting 1 mol of ethoxylated or propoxylated bisphenol A, decanediol or dodecanediol in 33 to 55% by weight with 2 mol of isophorone diisocyanate (IPDI), and then with 2 mol of 2-hydroxyethyl methacrylate (HEMA) or hydroxypropyl methacrylate (HPMA), (c) 0% by weight of further di(meth)acrylate monomers (d) At least one ABA or AB block copolymer comprising 2 to 10% by weight, wherein the A block is composed of oligomer polycaprolactone, poly(2,6-dimethyl-1,4-phenylene oxide), poly(ethylene oxide), poly(propylene oxide), or poly(meth)acrylate building blocks, and the B block is composed of poly(dimethylsiloxane), poly(isoprene), poly(vinyl acetate), poly(isobutene), cis-poly(butadiene), or poly(ethylene) building blocks, (e) 0% core-shell polymer, (f) 0.1 to 5.0% by weight of at least one photoinitiator, and (g) 0.2-5% by weight of one or more additional additives Dental materials containing this are particularly preferred according to the present invention.

[0110] The dental material according to the present invention is characterized by having high fracture toughness and fracture work, as well as good flexural strength and a relatively high modulus of elasticity, as measured in water at 37°C, which corresponds to oral conditions. The material also has high transparency and low viscosity. It is particularly advantageous that the dental material retains high transparency and low internal pigmentation even after hardening.

[0111] In contrast, core-shell polymers, which are used as impact-resistant modifiers in conventional technologies, typically result in a more or less obvious reduction in transparency, making them unsuitable for additive processes. Block copolymers (d) can improve fracture toughness, but it has been found that the reduction in transparency is relatively small compared to core-shell polymers. Furthermore, since much less block copolymer (d) is required to achieve the desired fracture toughness compared to core-shell polymers, block copolymers (d) make it possible to produce materials with high transparency, making them exceptionally suitable for additive processes.

[0112] The effect of block polymer (d) on increasing fracture toughness is due to the crosslinking density ν of the material. c is 300-5000 mol / m³ 3 Preferably 400-3000 mol / m³ 3 This is particularly noticeable within this range. Higher crosslinking density increases flexural strength and modulus, but consequently decreases the fracture strength of the polymer. Reducing crosslinking density increases fracture toughness, but has an unfavorable effect on flexural strength and modulus.

[0113] A preferred range of crosslinking density is achieved by using urethane di(meth)acrylate telekel(b) having a number-average molar mass of 750-2000 g / mol as the crosslinking agent, and the crosslinking density can be fine-tuned by adding small amounts of monomer di(meth)acrylate.

[0114] According to the present invention, materials having a transparency of ≥60%, preferably ≥70%, and most preferably ≥80%, and a viscosity of ≤10.0 Pa·s, preferably ≤5.0 Pa·s, are particularly preferred. Transparency is measured according to the ISO 10526:1999 standard as described above. Viscosity is determined using a cone-plate viscometer as described above.

[0115] After curing, the material according to the present invention has a pressure of 1.1 MPa·m 1 / 2 More preferably 1.2 MPa·m 1 / 2 More preferably, 1.4 MPa·m 1 / 2 Superb destructive toughness K max , and 250 J / m 2 More preferably 300 J / m 2 More preferably, 400 J / m 2 They possess an extremely high fracture work (FW). Therefore, workpieces produced from these materials are highly resistant to deformation without fracturing. In core-shell polymers, high transparency cannot be achieved in conjunction with a high fracture work.

[0116] Fracture toughness K maxThe determination of the work of fracture (FW) is performed in a three-point bending test with a support span of 32 mm, in accordance with ISO 20795-1:2013. max And the determination of FW is the stress intensity factor K 1C Based on the theoretical principles of fracture toughness K max This is the greatest factor in stress expansion, also known as the stress expansion coefficient at maximum load, and is calculated as follows.

number

number

number

[0117] The destructive work FW (destructive work, total destructive work) is calculated as follows:

number

[0118] After curing, the material according to the present invention has good flexural strength and relatively good flexural modulus, as well as good fracture toughness and high work of fracture. Molded parts obtained by curing the material according to the present invention have high rigidity and resist deformation with a high level of resistance without fracturing. After curing, it is preferable to have a material having a flexural strength of at least 40 MPa, particularly preferably 50 MPa or greater, and very preferably 60 MPa or greater, as determined according to ISO 20795-1:2013. Furthermore, the cured material preferably has a flexural modulus of at least 1000 MPa, preferably 1300 MPa or greater, particularly preferably 1500 MPa or greater, very preferably 2000 MPa or greater, and most preferably 2500 MPa, as determined according to ISO 20795-1:2013. Furthermore, the material has a flexural modulus of 1.1 MPa·m 1 / 2 Or greater than that, preferably 1.2 MPa·m 1 / 2 Or greater than that, particularly preferably 1.4 MPa·m 1 / 2 or greater fracture toughness K max , and 250 J / m 2 Or greater than that, preferably 300 J / m 2 Or greater than that, particularly preferably 400 J / m 2 Or it has a greater breaking power FW. Therefore, it has a bending strength of 60-100 MPa, a bending modulus of 2000-2500 MPa, and 1.4-2.5 MPa·m. 1 / 2 Fracture toughness K max and 400~800 J / m 2 Materials having a destructive work FW are particularly preferred.

[0119] According to a particularly preferred embodiment of the present invention, after curing, the material has a bending strength of 50 MPa or greater and 250 J / m² as measured according to ISO 20795-1:2013. 2 Or a greater destructive work and at least 1.2 MPa·m 0.5 K max It has a value (the greatest factor in stress expansion).

[0120] Due to the above-described properties, the materials according to the present invention are exceptionally suitable as dental materials, for example, as prosthetic or veneer materials, particularly for the production or repair of dental molded parts such as dental restorations, prostheses, artificial teeth, inlays, onlays, crowns, bridges, drill templates, splints (bite splints), trial bodies, and dental orthodontic devices such as plastic orthodontic splints, so-called aligners and positioners. The molded parts mentioned are also subject to the present invention. The dental materials according to the present invention are preferably used outside the oral cavity, i.e., non-therapeuticly.

[0121] Further subjects of the present invention are processes for producing dental molded parts, in particular processes for producing dental molded parts as described above, wherein light is used to cure the composition according to the present invention in order to produce dental molded parts. The production or repair of dental molded parts is preferably carried out outside the oral cavity, particularly preferably by an additive process, and most particularly preferably by a lithography-based process such as 3D printing or stereolithography.

[0122] Stereolithographic generation of molded parts is preferably performed by directly or indirectly digitizing the tooth(s) to be restored using a computer to create a virtual image of the tooth's condition, then constructing a model of the dental restoration or prosthesis using a computer based on this image, and subsequently generating this model by additive stereolithographic manufacturing.

[0123] Once a virtual model of the dental workpiece to be produced is created, the composition according to the present invention is polymerized by selective light irradiation. The dental restoration or prosthesis is preferably constructed in layers by successively polymerizing a plurality of thin layers having a desired cross-section. After the lamination construction of the restoration or prosthesis, excess residual resin is preferably removed. This can be done by a suitable mechanical process (e.g., centrifugation or sandblasting) or by treatment with a suitable solvent such as an alcohol such as ethanol or isopropanol, a ketone such as acetone, or an ester such as ethyl acetate. Subsequently, post-tempering is preferably performed by heating the workpiece, or particularly preferably, for example, at 405 nm and 160 mW / cm². 2 This is done by irradiating with light of a suitable wavelength, such as light of a certain intensity. When using two types of photoinitiators, irradiation at two different wavelengths is advantageous. The workpiece is heated to a temperature above 50°C, preferably simultaneously or in a subsequent step. Mechanical properties can be improved through photochemical and / or thermal post-tempering.

[0124] The present invention will be described in more detail below with reference to examples. [Examples]

[0125] (Example 1) Synthesis of 2-(2-biphenyloxy)-ethyl methacrylate (aromatic monomethacrylate) Stage 1: 2-(2-biphenyl)-oxyethanol [ka] In a reactor with a double jacket, 2.55 kg (15.0 mol) of 2-phenylphenol, 0.12 kg (0.75 mol) of potassium iodide, and 0.17 kg (0.75 mol) of benzyltriethylammonium chloride were added to an aqueous solution of 0.90 kg (22.5 mol) of sodium hydroxide in 15.0 kg of water. The solution was heated to 60 °C (internal temperature), and at the same time, the dropwise addition of 1.81 kg (22.5 mol) of 2-chloroethanol was started. After the addition was completed, the batch was stirred at 60 °C for 48 hours. For work-up, the batch was diluted with 6.0 l of toluene, and after phase separation, the aqueous phase was extracted two more times with 3.0 l of toluene each time. The combined toluene phases were washed three times with 4.0 l of 1N sodium hydroxide solution each time, three times with 4.0 l of 1N hydrochloric acid each time, and three times with 3.0 l of water each time. The toluene was distilled off under vacuum. After recrystallization from toluene, 2.77 kg (yield 86%) of 2-(2-biphenyl)-oxyethanol was obtained as a colorless crystalline solid (m.p.: 74 - 75 °C) with a purity (GC) > 99%. 1 H-NMR (400 MHz, CDCl3) δ (ppm) = 1.86 (t, J = 6.5 Hz, 1H, OH), 3.78 - 3.81 (m, 2H, HOCH2), 4.04 (t, J = 4.6 Hz, 2H, OCH2), 6.98 - 7.08, 7.28 - 7.34, 7.38 - 7.42 and 7.50 - 7.52 (4 m, 2H, 3H, 2H, 2H, =CH). 13 C-NMR (100 MHz, CDCl3) δ (ppm) = 61.4 and 70.3 (OCH2), 113.5 (C-6), 121.7 (C-4), 127.1, 128.7 and 131.0 (C-3, C-5, C-4’), 128.1 and 129.4 (C-2’, C-3’, C-5’, C-6’), 131.5 and 138.4 (C-2, C-1’), 155.4 (C-1). IR (diamond ATR): ν(cm -1)=3329(br,m,OH),3056(m,=CH),2918 and 2866(m,CH2),1596 and 1584(m,C=C),1502 and 1483(s,aromatic compounds),1431(s,CH2),1260 and 1077(s,COC),1054(s,COH),749,730 and 700(vs,=CH).

[0126] Stage 2: 2-(2-biphenyloxy)-ethyl methacrylate [ka] In a double-jacketed reactor, 0.75 kg (7.4 mol) of triethylamine, 37.9 g (0.31 mol) of 4-dimethylaminopyridine, and 0.35 g of 2,6-di-tert-butyl-4-methylphenol were added to 1.33 kg (6.2 mol) of 2-(2-biphenyl)-oxyethanol in a 13.0 L solution of methylene chloride. A solution of 1.14 kg (7.4 mol) of methacrylic anhydride was added dropwise at 0°C (internal temperature), and the mixture was stirred at this temperature for a further 2 hours, followed by stirring at 20°C for 20 hours. The solution was then washed three times with 4.0 L of 1N hydrochloric acid, three times with 4.0 L of 1N sodium hydroxide solution, and three times with 4.0 L of water. The organic phase was stabilized with 0.09 g of phenothiazine. After removing the solvent, 1.71 kg (98% yield) of 2-(2-biphenyloxy)-ethyl methacrylate (BPOEMA) was obtained as a nearly colorless oil with a purity (GC) of 96.45%. 1 H-NMR (400 MHz, CDCl3) δ (ppm) = 1.93 (s, 3H, CH3), 4.19 and 4.41 (2 t, each J = 4.8 Hz, each 2H, OCH2), 5.55 and 6.08 (2 s, each 1H, =CH2), 6.95-7.06, 7.26-7.30, 7.33-7.37 and 7.52-7.55 (4 m, 2H, 2H, 3H, 2H, =CH). 1313C-NMR (100 MHz, CDCl3) δ (ppm) = 18.3 (CH3), 63.0 and 66.5 (OCH2), 113.1 (C-6), 121.7 (C-4), 126.0 (C=CH2), 126.9, 128.6, 131.1 (C-3, C-5, C-4’), 127.9 and 129.6 (C-2’, C-3’, C-5’, C-6’), 131.3 and 138.3 (C-2, C-1’), 136.1 (C=CH2), 155.4 (C-1), 167.2 (C=O). IR (diamond ATR): ν (cm -1 ) = 3027 (w, =CH), 2955 and 2900 (w, CH2, CH3), 1716 (vs, C=O), 1636 (m, C=C メタクリル ), 1598 and​​​​​​​​​​​​​​​​​​​​​​​​​​​ A mixture of 1 equivalent of diol, 2 equivalents of isophorone diisocyanate (IPDI), and 700 ppm of Metatin 712 (relative to IPDI) was heated to 40°C. The diol was completely dissolved, and the mixture was heated to approximately 110°C. After the exothermic reaction subsided, the mixture was stirred at a bath temperature of 80°C for 1 hour before adding 2 equivalents of 2-hydroxyethyl methacrylate (HEMA, stabilized with 30 ppm of BHT (relative to 100% of the product) dropwise. After the exothermic reaction subsided again, stirring was continued at 90°C for a further 10 minutes. Completion of the reaction was checked by IR and NMR spectroscopy. The adduct was obtained as a very viscous to brittle colorless resin.

[0129] A. 1,10-Decanediol-IPDI-HEMA adduct (1:2:2), isomer mixture (DMA Telekel 1, molar mass: 879.15 g / mol) [ka] 1,10-decanediol was used as the diol. 1 H NMR (400 MHz, CDCl3): δ (ppm) = 0.85-0.97, 1.01-1.06, 1.19-1.38 and 1.59-1.75 [4 m, 46H, (CH2)8, CH 2, cycl. CH 3, 環 ), 2.03 (s, 6H, CH 3, メタクリル ), 2.81-2.98 and 3.20-3.33 (2 m, 4H, NCH2), 3.65-3.88 [m, 2H, NCH], 3.98-4.11 (m, 4H, OC H 2(CH2)8), 4.26-4.40 (m, 8H, O(CH2)2O), 4.57-4.94 (m, 4H, NH), 5.60 and 6.14 (2 s, each 2H, =CH2). IR (Diamond ATR): ν (cm -1)=3341(br,NH),2927 and 2856(m,CH),1695(vs,C=O),1638(m,C=C),1526(s,NH),1456(m,CH2,CH3),1366(m,CH3),1236(CN),1167 and 1039(s,m,COC),942(m,=CH),774[m,(CH2)8].

[0130] B. Bisphenol A-IPDI-HEMA adduct (1:2:2), isomer mixture (DMA Telekel 2, molar mass: 1049.31 g / mol) [ka] A bisphenol A derivative having a pendant-type isopropoxy group according to the following formula was used as the diol. [ka] 1 H NMR (400 MHz, CDCl3): δ (ppm) = 0.86-1.06, 1.18-1.21, 1.29-1.40 and 1.62-1.75 [4 m, 42H, CH 2, cycl. , CH3), 1.95 (s, 6H, CH 3, メタクリル ), 2.87-2.99 and 3.19-3.36 (2 m, 4H, NCH2), 3.67-3.88 [m, 2H, NCH], 3.91-4.03 and 4.09-4.22 (2 m, 4H, OC H 2CH), 4.26-4.40 and 4.50-5.18 (2 m, 14H, O(CH2)2O, OCH2C H , NH), 5.59 and 6.15 (2 s, 2H each, =CH2), 6.80 and 7.12 (2 d, 4H each, =CH). IR (Diamond ATR): ν (cm -1)=3341(br,NH),2955 and 2860(m,CH),1705(vs,C=O),1640(w,C=C),1608(w,aromatic compound),1507(s,NH),1456(m,CH2,CH3),1385(m,CH3),1231(CN),1155 and 1043(s,m,COC),941(m,=CH),829(m,=CH 芳香族化合物 ).

[0131] (Example 3) Synthesis of PCL(1600)-b-PDMS(3200)-b-PCL(1600) block copolymer (PO-277) Stage 1: Tetramethylammonium 3-aminopropyldimethylsilanoate Under a protective gas atmosphere, a mixture of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (2.49 g, 10.0 mmol) and tetramethylammonium hydroxide pentahydrate (3.62 g, 20 mmol) in tetrahydrofuran (THF; 10 ml) was heated under reflux for 3 hours. The solvent was removed by distillation, and the residue was heated to 50°C under a precise vacuum. The yellowish residue was recrystallized from THF (20 ml). 3.17 g (15.4 mmol; 77%) of a white solid was obtained. 1 H-NMR (CDCl3, 400 MHz): δ = 3.16 (s, 12H; N + -CH3), 2.37 (t, 2H; J = 7.1 Hz; N-CH2), 1.28 (m, 2H; CH2), 0.14 (m, 2H; Si-CH2), -0.33 (s, 6H; Si-CH3). Stage 2: Polydimethylsiloxane-αω-dipropyl-3-amine:PDMS(3200)

[0132] Under a protective gas atmosphere, a mixture of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (4.98 g, 20.0 mmol) and octamethylcyclotetrasiloxane (12.00 g, 40 mmol) was heated to 80°C. Tetramethylammonium 3-aminopropyldimethylsilanoate (20 mg) was added, and stirring was continued at 80°C. After 30 minutes, octamethylcyclotetrasiloxane (56.00 g, 0.192 mol) saturated with argon was slowly added dropwise. The reaction mixture was stirred at 80°C for a further 18 hours, and then heated to 150°C for 30 minutes to decompose the catalyst. The volatile components were then removed by precision vacuum. 65.30 g (88%) of colorless oil was obtained. 1 H-NMR (CDCl3, 400 MHz): δ =2.64 (t, 4H; J = 7.0 Hz; N-CH2), 1.43 (m, 4H; CH2), 0.51 (m, 4H; Si-CH2), 0.05 (s, 250H; Si-CH3). Stage 3: PCL(1600)-b-PDMS(3200)-b-PCL(1600) block copolymer

[0133] A mixture of PDMS (3200) (20.00 g) and ε-caprolactone (20.40 g) was heated to 80°C. After 1 hour, tinbis(2-ethylhexanoate) (10 mg) was added, and the bath temperature was gradually increased to 130°C over 30 minutes. The now clear reaction mixture was stirred at 130°C for a further 5 hours. The volatile components were then removed by distillation under a precise vacuum. 39.50 g (98%) of the block copolymer was obtained as a waxy, slightly yellowish solid. 1H-NMR (CDCl3, 400 MHz): δ = 3.99 (t, 55H; J = 6.8 Hz; O-CH2), 3.57 (t, 4H; J = 6.8 Hz; HO-CH2), 3.15 (q, 4H; J = 6.8 Hz; N-CH2), 2.24 (t, 55H; J = 7.5 Hz; C(O)-CH2), 2.10 (t, 4H; J = 7.5 Hz; N-CH2), 1.58 (m, 118H; CH2), 1.32 (m, 59H; CH2), 0.46 (m, 4H; Si-CH2), 0.02 (s, 250H; Si-CH3).

[0134] (Example 4) Synthesis of PMMA(1200)-b-PDMS(3200)-b-PMMA(1200) block copolymer Stage 1: α,ω-(2-bromoisobutyrylaminopropyl)-poly(dimethylsiloxane) α-bromoisobutyrate bromide (1.44 g; 6.24 mmol) was added dropwise to a solution of PDMS (3200) (6.66 g; 2.08 mmol) and triethylamine (0.84 g; 8.44 mmol) dissolved in THF (100 ml) at 0°C. The reaction mixture was stirred for 2 hours while cooling on ice, and then stirred at ambient temperature for 18 hours. The suspension was filtered, and the filtrate was concentrated using a rotary evaporator. The colorless oil was dissolved in dichloromethane (100 ml), washed with saturated Na2CO3 aqueous solution (50 ml twice), hydrochloric acid (0.2 N, 50 ml twice), and saturated NaCl aqueous solution (100 ml), dehydrated with anhydrous sodium sulfate, filtered, and concentrated using a rotary evaporator. Volatile components were removed by precision vacuum. 6.32 g (1.81 mmol; 87%) of a slightly yellowish liquid was obtained. 1 H-NMR (CDCl3, 400 MHz): δ = 3.22 (m, 4H; N-CH2), 1.92 (s, 12H; C-CH3), 1.54 (m, 4H; CH2), 0.53 (m, 4H; Si-CH2), 0.05 (s, 258H; Si-CH3). Stage 2: PMMA(1200)-b-PDMS(3200)-b-PMMA(1200) block copolymer

[0135] Under inert gas conditions, toluene (50 ml) was added to α,ω-(2-bromoisobutyrylaminopropyl)-poly(dimethylsiloxane) (6.22 g; 1.78 mmol), copper(I) chloride (0.35 g; 3.56 mmol), and N,N,N',N”,N”-pentamethyldiethylenetriamine (0.62 g; 3.56 mmol), and the solution was degassed. Methyl methacrylate (7.78 g; 77.7 mmol) was added. The solution was stirred at ambient temperature for 30 minutes, then heated to 90°C for 20 hours. After cooling, the solution was filtered through neutral aluminum oxide. The filtrate was concentrated using a rotary evaporator. The residue was dissolved in dichloromethane and filtered through silica gel. The filtrate was concentrated using a rotary evaporator, and the residue was dried in a precision vacuum. 8.77 g (1.49 mmol; 84%) of the block copolymer was obtained as a yellowish solid. 1 H-NMR (CDCl3, 400 MHz): δ = 3.53 (s, 72H; O-CH3), 3.28-3.03 (m, 4H; N-CH2), 2.20-1.12 (m, 64H; C-CH3, CH2), 1.13-0.63 (m 72H, CH3), 0.55-0.40 (m, 4H; Si-CH2), 0.0 (s, 252H, Si-CH3).

[0136] (Example 5) Synthesis of PCL(2500)-b-PDMS(3200)-b-PCL(2500) block copolymer A mixture of PDMS (3200) (20.00 g) and ε-caprolactone (30.60 g) was heated to 80°C. After 1 hour, tinbis(2-ethylhexanoate) (10 mg) was added, and the bath temperature was gradually increased to 130°C over 30 minutes. The resulting clear reaction mixture was stirred at 130°C for a further 5 hours. The volatile components were then removed by distillation under a precise vacuum. 49.00 g (97%) of a slightly yellowish, waxy solid was obtained. 1H-NMR (CDCl3, 400 MHz): δ = 3.99 (t, 86H; J = 6.8 Hz; O-CH2), 3.57 (t, 4H; J = 6.8 Hz; HO-CH2), 3.15 (q, 4H; J = 6.8 Hz; N-CH2), 2.24 (t, 86H; J = 7.5 Hz; C(O)-CH2), 2.10 (t, 4H; J = 7.5 Hz; N-CH2), 1.60-1.54 (m, 180H; CH2), 1.34-1.29 (m, 90H; CH2), 0.51-0.40 (m, 4H; Si-CH2), 0.02 (s, 250H; Si-CH3).

[0137] (Example 6) Synthesis of PCL(3200)-b-PDMS(3200)-b-PCL(3200) block copolymer A mixture of PDMS (3200) (15.00 g) and ε-caprolactone (30.60 g) was heated to 80°C. After 1 hour, tinbis(2-ethylhexanoate) (10 mg) was added, and the bath temperature was gradually increased to 130°C over 30 minutes. The now clear reaction mixture was stirred at 130°C for a further 5 hours. The volatile components were then removed by distillation under a precise vacuum. 44.20 g (97%) of a slightly yellowish, waxy solid was obtained. 1 H-NMR (CDCl3, 400 MHz): δ = 3.99 (t, 106H; J = 6.8 Hz; O-CH2), 3.57 (t, 4H; J = 6.8 Hz; HO-CH2), 3.15 (q, 4H; J = 6.8 Hz; N-CH2), 2.24 (t, 106H; J = 7.5 Hz; C(O)-CH2), 2.10 (t, 4H; J = 7.5 Hz; N-CH2), 1.60-1.54 (m, 220H; CH2), 1.34-1.29 (m, 110H; CH2), 0.51-0.40 (m, 4H; Si-CH2), 0.02 (s, 250H; Si-CH3).

[0138] (Example 7) Polymerization and preparation of SL resin The components listed in Table 1 were homogeneously mixed in the quantities indicated. To this end, all solid components (block copolymer or core-shell particles, photoinitiator) were dissolved in the monomer while stirring in a planetary mixer or Speedmixer, and heating to 50°C as needed. Then, urethane dimethacrylate Terekel was added, and stirring was continued until a homogeneous mixture was achieved. The block copolymer was incorporated into the mixture without issue. For the incorporation of core-shell particles, the mixture was further homogenized for 30 minutes at a rotation speed of 3000 rpm using a rotor-stator mixer (Ultra-Turrax T-25). The mixture was then degassed using a planetary mixer.

[0139] Test specimens were produced using a bottom-up process with formulations No. 5 and No. 6 on a stereolithographic printing press (PrograPrint PR5, from Ivoclar Vivadent AG, Schaan, Liechtenstein). The press used DLP techniques in the layer construction at a wavelength of 388 nm and an output of 10 mW / cm². 2 The samples were exposed using a pixel size of 50 μm. The layer thickness was 100 μm in all cases. Adhering residual resin was removed using isopropanol. To this end, the specimens were cleaned twice in fresh isopropanol with agitation (first bath 10 minutes, second bath 5 minutes) along with the build platform (PrograPrint Stage) using a PrograPrint Clean device (from Ivoclar Vivadent AG, Schaan, Liechtenstein), and immediately afterward blow-dried with compressed air. The specimens were then post-tempered by exposure to light at a wavelength of 405 nm for 90 seconds. This was done using a PrograPrint Cure device (from Ivoclar Vivadent AG, Schaan, Liechtenstein; software: ProArt Print Splint, 2020). The specimens were then removed from the build platform.

[0140] Using the remaining compositions in Table 1, specimens were prepared in a mold and cured by irradiating both sides with a dental light source (PrograPrint Cure, Ivoclar Vivadent AG, Schaan, Liechtenstein; software: ProArt Print Splint, 2020).

[0141] Further machining and storage of the test specimens were carried out in accordance with the relevant provisions of the details mentioned below. Flexural strength (FS) and flexural modulus (FM) were determined according to ISO standard ISO-4049 (Dental - Polymer-based filling, restorative and routing materials). For this purpose, the test specimens were pre-stored dry at room temperature for 24 hours or in water at 37°C for 24 hours. Furthermore, flexural strength and flexural modulus were measured according to ISO standard 20795-1:2013 (Dental - Base polymers - Part 1: Denture base polymers). Accordingly, prior to measurement, the test specimens were stored in deionized water at 37°C for 50 hours, and then measured in water at 37°C in a thermostat-controlled bath. Fracture toughness K max The determination of the destructive work FW was performed in accordance with ISO 20795-1:2013. The measurement results are shown in Table 2.

[0142] Formulations No. 1 and No. 10 are reference examples and do not contain core-shell polymers or block copolymers. While these reference examples exhibit good flexural strength and good flexural modulus, their fracture toughness and work of fracture values ​​are insufficient for the intended stereolithographic application and therefore unsuitable. Examples No. 3, No. 4, and No. 14 all contain core-shell polymer particles. In all cases, the addition of particles improves fracture toughness K max This also leads to improvements in the breakdown workflow (FW).

[0143] In Example No. 14, 5% by weight of core-shell particles were added to formulation No. 10. The addition of the core-shell polymer resulted in not only an improvement in fracture toughness but also a significant decrease in transparency. In Examples No. 12, No. 13, and No. 15, in each case, 5% by weight of block copolymer was added as an impact resistance modifier instead of core-shell particles. Table 2 shows that in all cases, the block copolymer provided a much greater improvement in fracture toughness than the core-shell particles, but the decrease in transparency was relatively small. Example No. 11 shows that the addition of 3% by weight of block copolymer is sufficient to achieve a similar improvement in fracture toughness as that of 5% by weight of core-shell particles.

[0144] A comparison of Examples No. 2 and No. 3 shows that, in this case as well, the addition of 3 wt% block copolymer results in almost the same improvement in fracture toughness as 5 wt% core-shell particles. Example No. 2 is characterized by higher transparency compared to Example No. 3, and it is recognized that the use of block copolymer makes it possible to produce materials with high fracture toughness and transparency.

[0145] A comparison of Examples No. 3 and No. 4 shows that increasing the amount of core-shell particles to 5-10% by weight can further improve fracture toughness, but this is accompanied by a further decrease in transparency. [Table 1] [Table 2]

Claims

1. at least one ABA or AB block copolymer (d), at least one monofunctional radically polymerizable monomer (a), and at least one radically polymerizable urethane di(meth)acrylate telechelate (b) having a number average molar mass of 750 to 2000 g / mol according to the general formula (II) 【Chemistry 19】 wherein the variables have the following meanings: R 1 and R 2 are independently in each case H or methyl; R 3 and R 4 are independently in each case H or methyl; x and y are each independently an integer from 1 to 11; n is 1, 2 or 3; Z is, 【Chemistry 20】 and DA is a structural element derived from the diol HO-DA-OH by cleaving a hydrogen atom from a hydroxyl group, said diol HO-DA-OH being one of the following compounds: ethoxylated or propoxylated bisphenol A, o- or p-diphenyl, with 2 to 6 ethoxy or propoxy groups, C 2 -C 18, which may contain 1 to 4 O or S atoms in the carbon chain. alkanediols, ethoxylated or propoxylated bisphenol A having 2, 3 or 4 ethoxy or propoxy groups, hexane-1,6-diol, octane-1,8-diol, nonane-1,9-diol, decane-1,10-diol, undecanediol or dodecane-1,12-diol, tetra- or pentaethylene glycol, cyclic or polycyclic aliphatic diols, cyclohexanediol, norbornanediol, tricyclodecanediol and tricyclodecane dimethanol (octahydro-4,7-methano-1H-indene dimethanol).

2. In each case, relative to the total mass of said material, (a) 30 to 70% by weight of at least one aromatic bicyclic or tricyclic mono(meth)acrylate; (b) 20 to 60% by weight of at least one urethane di(meth)acrylate telechel having a number average molar mass of 750 to 2000 g / mol, (c) 0 to 30 wt. % of di(meth)acrylate monomer(s); (d) 1 to 12 wt. % of at least one ABA and / or AB block copolymer, wherein the A block(s) are homogeneously miscible with the mixture of components (a)-(c) and the B block is not homogeneously miscible with the mixture of components (a)-(c); and (e) 0.1 to 5.0% by weight of at least one initiator for radical polymerization. The radically polymerizable dental material of claim 1 , comprising:

3. As component (a), at least one aromatic bicyclic or tricyclic monomethacrylate of formula (I) 【Chemistry 18】 wherein the variables have the following meanings: A is an aromatic group having 6 to 15 carbon atoms or a bicyclic or tricyclic aliphatic group having 7 to 10 carbon atoms, and A may be unsubstituted or may contain one or more C 1 ~C 5 Alkyl group, C 1 ~C 5 may be substituted by alkoxy groups and / or chlorine atoms; R is hydrogen or methyl; X 1 , X 2 are, independently of one another, absent in each case or an ether, ester or urethane group; Y 1 If does not exist, then X 1 does not exist, and Y 2 If does not exist, then X 2 does not exist; Y 1 , Y 2 are, independently of one another, absent in each case or a branched or linear aliphatic hydrocarbon radical having 1 to 10 carbon atoms, which may be interrupted by 1 to 3 oxygen atoms. The radically polymerizable dental material of claim 1 , comprising:

4. As component (a), 2-phenoxyethyl (meth)acrylate, 2-(o-biphenyloxy)ethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, phenethyl (meth)acrylate, 2-[(benzyloxycarbonyl)-amino]-ethyl (meth)acrylate, 2-[(benzylcarbamoyl)-oxy]-ethyl (meth)acrylate, 1-phenoxypropan-2-yl (meth)acrylate, and 2-(p-cumylphenoxy)-ethyl (meth)acrylate, 2-(benzyloxy)ethyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, 4. The radical polymerizable dental material of claim 3, comprising one or more of the following compounds: acrylate, phenoxypropyl (meth)acrylate, 2-benzyloxyethyl (meth)acrylate, 2-benzoyloxyethyl (meth)acrylate, 2-(meth)acryloyloxybenzoic acid methyl ester, tricyclodecane (meth)acrylate, tricyclodecane methyl (meth)acrylate, 2-(p-cumylphenoxy)ethyl (meth)acrylate, 4,7,7-trimethylbicyclo[2.2.1]heptanyl (meth)acrylate, octahydro-1H-4,7-methanoinden-5-yl (meth)acrylate or mixtures thereof.

5. 3. The radically polymerizable dental material according to claim 2, comprising as component (d) at least one ABA and / or AB block copolymer, the A block being an oligomer composed of one or more of the following monomers: cycloaliphatic esters or ethers, arylene oxides, alkylene oxides, radically polymerizable monomers, α,β-unsaturated acids and α,β-unsaturated acid esters, and the B block being a polysiloxane oligomer and / or a polyvinyl oligomer and / or a polyalkene oligomer and / or a polydiene oligomer.

6. 6. The radically polymerizable dental material according to claim 5, comprising as component (d) at least one ABA and / or AB block copolymer, the A blocks being oligomeric polycaprolactone (PCL), poly(2,6-dimethyl-1,4-phenylene oxide), poly(ethylene oxide), poly(propylene oxide) or poly(meth)acrylate building blocks and the B blocks being oligomeric poly(dimethylsiloxane) (PDMS), poly(isoprene), poly(vinyl acetate), poly(isobutene), cis-poly(butadiene) or poly(ethylene) building blocks.

7. 7. The radically polymerizable dental material according to claim 6, comprising as component (d) at least one ABA triblock copolymer of the PCL-b-PDMS-b-PCL and / or PMMA-b-PDMS-b-PMMA type with a molar ratio A:B of 0.1 to 5 and a molar mass of 3 to 25 kDa, 4 to 20 kDa, or 5 to 10 kDa.

8. as component (e) benzophenone, benzoin or a derivative thereof, an α-diketone or a derivative thereof, 9,10-phenanthrenequinone, 1-phenyl-propane-1,2-dione, diacetyl or 4,4′-dichlorobenzil, camphorquinone (CQ), 2,2-dimethoxy-2-phenylacetophenone or an α-diketone in combination with an amine reducing agent (4-(dimethylamino)-benzoic acid ester (EDMAB), N,N-dimethylaminoethyl methacrylate, N,N-dimethyl-sym.-xylidine or triethanolamine), monoacyltrialkylgermanium, diacyldialkylgermanium, tetraacylgermanium, tetraacylstannane, benzoyltrimethylgermanium, dibenzoyldiethylgermanium, bis(4-methoxybenzoyl)diethylgermanium, tetrakis(2-methylbenzoyl)germane or tetrakis(mesitoyl)stannane or mixtures thereof, Norrish Type I photoinitiators including acetophenone, 2,2-diethoxy-1-phenylethanone, benzoin ethers, Irgacure 651 (benzyl dimethyl ketal), hydroxyalkylphenylacetophenone, Irgacure 184 (1-hydroxycyclohexyl phenyl ketone), acylphosphine oxide or bisacylphosphine oxide, Irgacure TPO (2,4,6-trimethylbenzoyldiphenylphosphine oxide) or Irgacure 819 (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide), 2-benzyl-2-(dimethylamino)-4'-morpholinobutyrophenone (Irgacure 369) and / or 1-butanone-2-(dimethylamino)-2-(4-methylphenyl)methyl-1-4-(4-morpholinyl)phenyl (Irgacure 379).

3. The radically polymerizable dental material according to claim 2, comprising at least one photoinitiator selected from the group consisting of:

9. In each case, relative to the total mass of the material, the composition is as follows: (a) 30 to 70% by weight of at least one aromatic bicyclic or tricyclic mono(meth)acrylate; (b) 20 to 60% by weight of at least one urethane di(meth)acrylate telechel having a number average molar mass of 750 to 2000 g / mol, (c) 0 to 30 wt. % of di(meth)acrylate monomer(s); (d) 1 to 12 weight percent of at least one ABA or AB block copolymer; (e) 0.1 to 5.0% by weight of at least one initiator for radical polymerization; (f) 0 to 15 wt. % of core-shell polymer particles; (g) 0 to 20 weight percent of a filler; (h) 0 to 1.0 wt. % of an ultraviolet absorber; (i) 0 to 0.5% by weight of an optical brightener, and (j) 0 to 15% by weight of further additives 2. The radically polymerizable dental material according to claim 1, having

10. In each case, relative to the total mass of said material, (a) 40 to 61% by weight of 2-phenoxyethyl (meth)acrylate, 2-(o-biphenyloxy)ethyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-[(benzyloxycarbonyl)amino]ethyl (meth)acrylate, 1-phenoxypropan-2-yl (meth)acrylate, 2-(benzyloxy)-ethyl (meth)acrylate, 2-(methacryloyloxy)ethyl (meth)acrylate, 3-phenoxybenzyl (meth)acrylate, phenoxypropyl (meth)acrylate, 2-benzyloxyethyl (meth)acrylate, 2-benzoyloxyethyl (meth)acrylate, 2-(meth)acryloyloxybenzoic acid methyl ester, 2-phenylethyl (meth)acrylate, tricyclodecane (meth)acrylate, tricyclodecane methyl (meth)acrylate and / or 2-(p-cumylphenoxy)ethyl methacrylate, (b) 33 to 55% by weight of at least one urethane di(meth)acrylate telechel having a number-average molar mass of 750 to 2000 g / mol and at least 4 urethane groups, prepared by reacting 1 mol of ethoxylated or propoxylated bisphenol A, decanediol or dodecanediol with 2 mol of isophorone diisocyanate (IPDI) and then with 2 mol of 2-hydroxyethyl methacrylate (HEMA) or hydroxypropyl methacrylate (HPMA); (d) 2 to 10 weight percent of at least one ABA or AB block copolymer, the A blocks being composed of oligomeric polycaprolactone, poly(2,6-dimethyl-1,4-phenylene oxide), poly(ethylene oxide), poly(propylene oxide), or poly(meth)acrylate building blocks, and the B blocks being composed of poly(dimethylsiloxane), poly(isoprene), poly(vinyl acetate), poly(isobutene), cis-poly(butadiene), or poly(ethylene) building blocks; (e) 0.1 to 5.0 wt. % of at least one photoinitiator, and (g) 0.2 to 5 wt. % of one or more further additives and is substantially free of di(meth)acrylate monomers and core-shell polymer particles.

11. 2. The radically polymerizable dental material according to claim 1, having a transparency of ≧60% and a viscosity of ≦10.0 Pa·s at 25° C.

12. 300-5000mol / m 3 2. The radically polymerizable dental material according to claim 1, having a crosslink density after curing of